Controls on morphology of catchment-fan systems in the northwest margin of the Junggar Basin, northwest China - Zixiao Peng; Jianhua Qu; Zhijie Zhang; En Xie; Hongying Zhou; Li Wan; Dawei Cheng; Shunli Li; Xinghe Yu (Journal of Asian Earth Sciences, 2026)

The progress of mitochondrial function and transfer in stem cell regulation and therapy - Yubing Zhang; Zhuojian Qu; Zhiliang Guo; Lijuan Zhang; Hong Li; Xiaoyun Zhang; Xiumei Guan; Xiaodong Cui; Wenxu Wang; Min Cheng (Journal of Physiology and Biochemistry, 2026)

Mechanism of water and nutrient competition between shelterbelts and farmland under different irrigation patterns in the Hexi Corridor oasis area, China - Yulian Hao; Haiyang Xi; Wenju Cheng; Tengfei Yu; Baofeng Li; Tuo Han; Yuqing Chen; Linbo Qu; Zhehui Wang (Soil and Tillage Research, 2026)

Numerical investigation of waste collection behavior in octagonal aquaculture tanks of deep-sea aquaculture vessels under multi-degree-of-freedom excitations - Haoran Cheng; Dejun Feng; Yanfei Wu; Lianhui Wu; Jiajun Hu; Fuzhi Zu; Hongzhou Chen; Fukun Gui; Xiaoyu Qu (Ocean Engineering, 2026)

A research on the current blockage effects of unconventional jackets based on physical experiments - Qiangqiang Liu; Hongbing Liu; Xiaolong Qiu; Yuchen Lu; Haoyang Cheng; Chuanyang Zhao; Xianqiang Qu (Ocean Engineering, 2026)

The boosted light utilization and spatial charge separation efficiency of ZnIn2S4 photoanode for photoelectrochemical hydrogen evolution by synergistical action of non-metal plasmonic effect and charge transport channel - Kangwei Zhang; Guozhong Wei; Bufan Liu; Hongyu Wang; Ruoyi Jin; Lang Cheng; Ziyi Wang; Zhen Qu; Junli Fu; Guling Zhang; Wenzhong Wang (Journal of Environmental Chemical Engineering, 2026)

Balancing Ni site supply and interfacial oxygen migration on Ni–Fe–CeO2 catalysts for coke resistant dry reforming of methane - Xuanyu Ji; Yuqin Cheng; Qiufan Qu; Qinghui Yu; Xiong Zhou; Yu Yang; Wenli Song; Haoran Wang; Lu Yang (Fuel, 2026)

Polygonatum kingianum polysaccharides ameliorate cognitive impairments in alcohol-exposed obese mice in a sex-specific manner by regulating the gut microbiome and metabolome - Jiayao Lv; Yizhe Qu; Qixin Yan; Ken Cheng; Qingyang Wu; Jiayi Zhang; Xinting Duan; Shanshan Han; Honglei Tian; Lin Shi (Food Research International, 2026)

How do green certificate and carbon emission trading impact clean energy investment? Evidence from evolutionary game modeling - Lu-Tao Zhao; Shi-Tong Wang; Zhi Qu; Wei-Gang Zhao; Lei Cheng (Energy Policy, 2026)

Ecological risks from emerging contaminants in sewage: Assessment of plastisphere-driven ARGs dissemination and comparative treatment process efficiencies - Hongwei Yu; Lingbo Wang; Nan Shen; He Ji; Yu Cheng; Jing Qi; Chengzhi Hu; Jiuhui Qu (Chemical Engineering Journal, 2026)

A mineralizable and electroactive periosteum for promoting infected bone defect repair by remodeling the osteogenic microenvironment - Yangyang Qu; Linghanqing Wang; Xinyue Yang; Shixing Luo; Chongnan Yan; Nizhou Jiang; Yanchao Zhang; Jingyi Qu; Sida Chen; Yuanming Xiao; Yifeng Shang; Jun Li; et al. (Chemical Engineering Journal, 2026)

Alkaloids with chemotaxonomic value from Delphinium grandiflorum - Yufei Zhao; Nannan Li; Shengli Cheng; Biao Qu; Xin Xia (Biochemical Systematics and Ecology, 2026)

Determination of bearing capacity and failure envelope of helical pile in clay under combined loading - Fei Liu; Kaizhe Shang; Chaofan Liu; Songzhao Qu; Po Cheng; Chao Hou; Yanzhao Yuan; Ruiduo Li (Marine Georesources & Geotechnology, 2026)

Dynamic changes in suitable production areas of Angelica sinensis (Oliv.) Diels under environment and land use policies - Liu Jia; Qu Cheng; Pu Chunjuan; Liu Pei; Guo Sheng; Zhou Guisheng; Duan Jin-ao; Zhao Siyi; Feng Yanzhe; Yan Hui (Journal for Nature Conservation, 2026)

Recent advances and applications in integrated passive microfluidic platforms for circulating tumor cell detection - Zhengxian Dan; Ziwen Cheng; Chen Huang; Shijie Qu; Xinyi Wang; Huanhuan Shi (Chemical Engineering Journal, 2026)

Regulated external lithium supply enables high-energy sulfurized polyacrylonitrile-graphite fiber batteries - Tianrui Li; Chuanfa Li; Qian Ye; Yi Jiang; Longmei Ma; Jiaqi Wang; Yiqing Cheng; Kun Zhang; Jiahe Qu; Yingfan Chang; Shiqi Sun; Siwei Cao; et al. (Science Bulletin, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

Adaptive spatiotemporal infinite-dimensional Bayesian inversion for hull wave load fields under sparse measurement conditions - Weizhe Ren; Yao Wang; Jiahui Zhou; Yuchen Lu; Wenqiang Cheng; Xianqiang Qu; Baiqiao Chen (Ocean Engineering, 2026)

Deep Learning-Enhanced Adaptive Correntropy Factor Graph Optimization for robust UUV navigation - Sen Cheng; Yanyan Wang; Bin Sun; Haitao Zhu; Xianqiang Qu (Ocean Engineering, 2026)

Contamination levels, spatial distribution, and risk assessment of heavy metals and PCDD/Fs in fly ash from representative MSWIs in Zhejiang Province, China - Xuetong Qu; Yanan Wang; Kenan Chen; Xin Cheng; Jibo Dou; Yunfei He; Shuai Zhang; Jiafeng Ding; YuChi Zhong; Hangjun Zhang (Journal of Environmental Sciences, 2026)

Zoning policy performance in China: Network insights from 77 Yellow River counties in Shandong, China - Mimi Gong; Maofang Ran; Qiang Huang; Yan Cheng; Haonan Xia; Yihan Yao; Qian Wang; Wei Xiang; Meiying Jin; Zile Han; Jun Zhai; Xiaomin Li; et al. (Journal of Environmental Sciences, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

Settling velocity characteristics and model establishment of typical MPs under freshwater, saline and sediment conditions - Lingna Kong; Yuxia Li; Yankang Zhao; Qing Su; Yuyang Sun; Ling Qu; Xingxing Zhang; Jiayi Cheng; Xiaomeng Wang (Environmental Research, 2026)

Emeishan basalt’s contribution to heavy metals in topsoil (notably cadmium) in Southwest China from soil geochemistry evidence - Fang Yang; Liang Tang; Yang Li; Bo Cheng; Tim T. Werner; Lingfei Qu; Ke Cheng; Aiming Zhang; Junbo Wang; Guikai Li (Acta Geochimica, 2026)

Dynamics-Embedded Sparse Bayesian Inversion for Robust Transient Impact Identification in Marine Structures - Weizhe Ren; Yao Wang; Jiahui Zhou; Yuchen Lu; Yinong Tian; Wenqiang Cheng; Xianqiang Qu; Bai-Qiao Chen (Journal of Marine Science and Engineering, 2026)
To address load reconstruction misidentification caused by low-damping free-decay oscillations in thin-walled engineering structures under transient impact, a dynamics-embedded sparse Bayesian inference (DE-SBI) framework is developed for impact load reconstruction. The proposed method embeds a representative Duhamel temporal kernel into Gaussian temporal atoms and combines it with spatial Gaussian load atoms, finite-element modal strain mapping, and automatic relevance determination (ARD)-based sparse Bayesian inference. This formulation yields a dynamics-embedded spatiotemporal dictionary, which reduces the risk that conventional quasi-static dictionaries misinterpret structural ringing responses as sustained external loads. Controlled numerical validation on a representative stiffened plate structure shows that DE-SBI can effectively reconstruct the impact load histories and spatial distributions under single-impact, off-grid impact, and spatiotemporally overlapping dual-impact cases. Compared with Tikhonov regularization, Lasso regularization, and standard SBI, DE-SBI exhibits more stable identification performance in terms of correlation coefficient, peak error, and spatial relative error. Further analyses of parameter sensitivity, sensor layout, noise perturbation, and Duhamel temporal-kernel mismatch indicate that the method maintains good robustness under the considered controlled numerical conditions. These results provide an interpretable dynamics-embedded Bayesian inversion strategy for transient impact load identification under sparse-observation conditions.

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Stress field reconstruction of a floating nuclear power plant sparse sensing using a physics-informed gated spatial graph transformer - Weizhe Ren; Xiaolong Qiu; Jiahui Zhou; Yao Wang; Yinong Tian; Wenqiang Cheng; Xianqiang Qu; Baiqiao Chen (Ocean Engineering, 2026)

Structural snapshots of plant-specific KCS6-CER2 complex reveal the elongation mechanism of very-long-chain fatty acids - Yang Wang; Haiyan Wang; Xianpeng Yang; Yujiao Qin; Rangwei Xu; Ting Liu; Chunmei Shi; Hongyan Zhang; Linlin Zhong; Xiaolu Qu; Feng Zhu; Xiuxin Deng; et al. (Molecular Plant, 2026)

Pulmonary effect of 2D MXenes in mice: Immune cell responses and disrupted hematopoiesis - Gang Tang; Min Li; Jiexia Cheng; Ziniu Wang; Guangxuan Wang; Jianbo Shi; Jonathan W.C. Wong; Jie Gao; Dou Wang; Guohao Zhang; Li Zeng; Yanhua Wang; et al. (NanoImpact, 2026)

A novel nonlocal damage model for fluid-driven mixed-mode fracture propagation in poroelastic medium - Changxin Yang; Cheng Ma; Jianhua Qu; Zhaozhong Yang; Xin Yang; Bo Kang; Duo Yi (Computers and Geotechnics, 2026)

Numerical Research on Hydraulic Fracturing in Geothermal Reservoirs Considering the Effects of Thermal Stress and Natural Fractures Through the CDEM Model - Jiwei Wang; Cheng Zhai; Tiankui Guo; Xuliang Jia; Jizhao Xu; Ming Chen; Zhanqing Qu (Rock Mechanics and Rock Engineering, 2026)

Heterocyclic PAH pollution risks in stormwater overflows: Mechanistic elucidation of sediments as the key contributor - Tianyi Dong; Cheng Ye; Feiyang Ao; Yao Qu; Feifei Wang; Jan Hofman; Zuxin Xu; Wenhai Chu (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Splicing factor SC35 inhibits Nosema bombycis proliferation by regulating the alternative splicing of Bmupp1 - Qiong Yu; Qingsheng Qu; Shiyi Lu; Pingyang Wang; Li Sui; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

Cr(VI) bioreduction by fulvic acid-mineral-microbe interactions: The critical role of nitrogen-centered environmentally persistent free radicals - Cheng Yu; Xuantong Li; Chenchen Qu; Chunhui Gao; Yichao Wu; Jiangrong Xiao; Ke Dai; Peng Cai; Qiaoyun Huang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Phosphorylated chitosan in-situ ionic self-crosslinked sulfonated poly(etherether ketone) proton exchange membrane for direct methanol fuel cells” [Fuel 427(Part E) (2027) 140108] - Zhuo Li; Guoliang Liu; Fuqiang Hu; Ying Ou; Ting Qu; Yong Liu; Fan Cheng; Quanyuan Zhang; Zushun Xu; Hai Liu; Jie Wang (Fuel, 2026)

Decadal changes and drivers of soil and vegetation carbon in the dryland ecosystems of Northwestern China - Yuqing Chen; Haiyang Xi; Meng Zhu; Bin Wang; Wenju Cheng; Xinwei Yin; Yulian Hao; Linbo Qu; Zhehui Wang (CATENA, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

A robust INS/USBL/DVL integrated navigation method based on adaptive correlation entropy factor graph optimization - Sen Cheng; Yanyan Wang; Qinglong Zhao; Haitao Zhu; Xianqiang Qu (Ocean Engineering, 2026)

Highly efficient lithium separation from sodium-rich mother liquor enabled by novel phenylazophenol derivatives - Han Qu; Guofei Li; Zhiwen Cheng; Wanji Zhou; Chao Zhang (Journal of Water Process Engineering, 2026)

Crop-specific biogenic volatile organic compound emissions in China - Ying Zhou; Jing Cao; Jianlei Lang; Huijuan Fan; Wanting Zhang; Xinyu Qu; Yadong Wang; Dongsheng Chen; Shuiyuan Cheng (Journal of Environmental Sciences, 2026)

Progress in Degradation of Volatile Organic Compounds by Biochar Fillers - Miaomiao Qu; Renlei Zhou; Zhuowei Cheng; Qiwen Luo; Yuqi Feng; Yun Shi; Wenjun Wang; Jianmeng Chen; Minmin Zhang (Water, Air, & Soil Pollution, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Corrigendum to “Divergent summertime surface O3 pollution formation mechanisms in two typical Chinese cities in the Beijing-Tianjin-Hebei region and Fenwei Plain” [Sci. Total Environ. 870 (2023) 161868] - Chenlu Li; Qiang Cheng; Yitian Guo; Xingang Liu; Yu Qu; Junling An; Yafei Liu (Science of The Total Environment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Preparation of synthetic graphite from coal-based humic acid by catalytic graphitization as high-performance anode materials for lithium-ion batteries - Saidan Zhao; Baolin Xing; Yongzhi Liu; Hui Guo; Huihui Zeng; Xiaoxiao Qu; Song Cheng; Feng Shi; Chuanxiang Zhang; Yaowen Xing; Yijun Cao; Peng Li (Fuel, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

Optimization of fermentation conditions for recombinant McXyn0243 xylanase from Malbranchea cinnamomea and its application in producing xylooligosaccharides from sugarcane bagasse - Jinghao Ma; Lin Dai; Ruiwen Cheng; Fei Xiao; Yongbo Qu; Jianshan Fu; Jianhui Wen; Rana Abdul Basit; Dafeng Yin; Guangsen Fan (Biocatalysis and Agricultural Biotechnology, 2026)

Risk assessment, resistance monitoring and mechanism of field-evolved resistance to broflanilide in the tobacco cutworm, Spodoptera litura - Xiao Guo; Yilu Tong; Ren Li; Shengran Zhang; Daofeng Zhang; Cheng Qu; Xiaoli Ma; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Fluid flow and heat transfer during staged multi-cluster fracturing treatments along horizontal wells — Application for hydraulic fracture characterization using distributed temperature sensing - Cao Wei; Dan Qu; Haitao Li; Shiqing Cheng; Chang Liu; Hassan Hassanzadeh (Geothermics, 2026)

Driving factors and predictive model of dissolved N2O concentrations in a complex aquatic network - Li Zhang; Dongli She; Menghua Xiao; Yongchun Pan; Cheng Lu; Shenhao Qu; Taohong Cao; Yongqiu Xia (Environmental Research, 2026)

Ecological roles of lactic acid bacteria biodiversity and cross-feeding in shaping the flavor landscape of traditional Huangjiu fermentation - Chao-Jie Zhu; Yi-Ling Zhong; Yong-Zhu Zhang; Zhi-Chu Shan; Hong-Yan Qu; Fei Cheng; Wei Feng; Peng Wang; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Bioresource Technology, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Rainfall-driven shifts in disinfection byproduct precursors in eutrophic lakes: From algal to terrestrial sources - Fangyuan Jiang; Jiaqi Ran; Feifei Wang; Yao Qu; Kaidi Lai; Ruixin Qu; Wenyuan Yang; Cheng Ye; Wenhai Chu (Journal of Hazardous Materials, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

FeC particle electrodes derived from copper slag boost peroxymonosulfate activation for efficient antibiotic degradation: non-radical pathways mediated by 3d orbital electron reconstruction - Linjin Li; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Minhua Cheng; Nanqi Ren; Ping Lu; Minjie He; Jun Wang (Bioresource Technology, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Unveiling the kinetics and mechanism of carbonate radicals in antibiotic resistance dissemination - Hao Yang; Fangyuan Cheng; Yangjian Zhou; Tong Zhou; Linyi Fan; Zhengfeng Guo; Tingting Zhang; Dongyang He; Ya-nan Zhang; Jiao Qu (Water Research, 2026)

Phototransformation of benzodiazepines in water mediated by dissolved black carbon: Mechanisms and the structure-reactivity relationship - Zhi-Cheng Zhou; Bin Yang; He-Yun Fu; Xiao-Lei Qu; Pei-Zhe Sun; Yong Feng; Guang-Guo Ying (Water Research, 2026)

Role of multivalent iron in enhancing sodium percarbonate oxidation for alleviating membrane distillation fouling caused by shale gas produced water - Haiqing Chang; Yuan Huang; Suhua Gu; Xiaoxiang Cheng; Fangshu Qu (Water Research, 2026)

Carbonized polymer dots as drivers of modernization in Chinese Herbal Medicine - Linlin Zhang; Ying Cheng; Xin Yang; Xiaoyu Chang; Siyu Lu; Bai Yang; Xiaoli Qu (Science Bulletin, 2026)

Resistance mechanisms and fitness outcomes of tetraniliprole, one novel diamide insecticide, in a near-isogenic strain of Spodoptera litura (Lepidoptera: Noctuidae) - Peng Lu; Ren Li; Xiao Guo; Juan Tang; Yilu Tong; Shengran Zhang; Qi Su; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Overexpression of cytochrome P450 gene CYP402C18 contributes to the detoxification of dimpropyridaz, one novel pyridazine pyrazolecarboxamide insecticide, in the whitefly Bemisia tabaci Mediterranean cryptic species - Juan Tang; Ren Li; Zehua Wang; Peng Lu; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Nitrate dynamics in engineered plain polder–river networks driven by surface water–groundwater interactions - Shenhao Qu; Dongli She; Yongchun Pan; Menghua Xiao; Peng Chen; Junhan Zhao; Taohong Cao; Xinni Ju; Li Zhang; Cheng Lu; Yongqiu Xia (Journal of Hydrology, 2026)

A deep learning-based two-stage feature matching method for small celestial body 3D shape reconstruction - Falin Wu; Jingyao Yang; Guoxin Qu; Yushuang Liu; Haoxin Li; Yuting Cheng; Dongjing Yang (Icarus, 2026)

Deciphering the butylated hydroxytoluene dissolution behavior in solid-liquid systems through coupled experimental and molecular dynamic simulation approaches - Xing Wu; Xiaowei Cheng; Shiyu Sun; Jixu Ni; Yuan Han; Mengwen Qu; Baoshu Liu; Hua Sun (Food Chemistry, 2026)

Biomass reforming to H2 and formic acid via an off-field electrocatalysis - Xiaolei Qu; Qing-Nan Wang; Ben Chang; Chuchu Cheng; Shengqi Chen; Shihua Ye; Jun Chen; Can Li (Chemical Engineering Journal, 2026)

Harnessing β-glucans for immune regulation: Bridging structural diversity, therapeutic potential, and functional food development - Xue Wang; Linlin Ma; Chen Chen; Lina Ma; Xian Qu; Ai Ren; Yifa Zhou; Hairong Cheng (Carbohydrate Polymers, 2026)

A hyper-crosslinked ionic polymer catalyzing CO2 one-pot two-step to dimethyl carbonate via HCO3-/OH- synergy - Jingya Yang; Ming Sun; Qinghua Qu; Jiquan Liang; Cheng Fang; Lei Wang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2025)

A study of the effect of ammonia on the oxidation reactivity and structure of char from coal/ammonia co-pyrolysis - Dikun Hong; Yajing Guo; Changlong Qu; Yong Zhang; Liming Cui; Wenzhen Zhang; Wei Chu; Xingxing Cheng; Chunbo Wang (Fuel, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Multifunctional sutures coated with metal-phenolic networks for dynamic antibacterial and antioxidant therapy - Qianchen Huang; Dongyu Yu; Siyu Li; Renhai Zhao; Guangqi Cheng; Zhenghai Qu; Bin Wang; Shuang Wang; Pan He; Ling Li; Jiwei Li (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Surface free energy-driven adsorption enhancement: phenolic hydroxyl-modified porous polymeric resins for polar VOCs capture - Huijuan Liu; Hongchang Qu; Longfei Liu; Jiayao Cheng; Hongjie Wang (Chemical Engineering Journal, 2025)

Regulatory effects of organic compound L-glutamic acid on multi-scale structural characteristics of starch in high-quality wheat under post-anthesis drought stress - Gang Li; Jialian Wei; Kaiyong Fu; Mei Yan; Gelin Liu; Shiya Qu; Chunyan Li; Cheng Li (Carbohydrate Polymers, 2025)

An experimental investigation of local scour at squat, shallowly embedded subsea structures - Lili Qu; Hongwei An; Scott Draper; Phil Watson; Liang Cheng (Coastal Engineering, 2025)

Chemical constituents of Alchornea rugosa and their chemotaxonomic significance - Xin-Xin Liang; Ming-Hao Mao; Si-Cheng Jin; Jia-Yi Zhang; Lei Wu; Jiao-Ying Qu; Jiao-Jiao Pan; Xiang-Guo Meng (Biochemical Systematics and Ecology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Research on the Method of First Arrival Time Picking of Microseismic Signals and Inverse Location Based on Underground Water-Sealed Oil Reservoir - Fei Cheng; Daicheng Peng; Niannian Qu; Jiangping Liu (Rock Mechanics and Rock Engineering, 2025)

Design, synthesis and biological evaluation of novel dualaction statin conjugates with triglyceride and cholesterol lowering activities - Zheng Qu; Ye-Cheng Liu; Qi Suo; Xu Wang; Jin-Wen Huang; Zhuo Wu; Fan-Hong Wu (Molecular Diversity, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Partially empirical model-based water depth retrieval in shallow sea using GF5-AHSI hyperspectral remote sensing data: a case study on Meizhou Bay in Fujian Province, China - Xiaoai Dai; Yunfeng Shan; Cheng Li; Hao Chen; Tangrui Dai; Ge Qu; Tianyi Xie; Chengbo Tong; Htun Naing; Min Zhang (Frontiers of Earth Science, 2025)

Population Genomics and Climate Change Vulnerability in Two Sympatric Desert Rodents - Tian Tian; Jilong Cheng; Yu Zhang; Lin Xia; Yilin Chen; Fangyuan Yang; Zhixin Wen; Yaqian Cui; Weibo Wang; Xueying Zhang; Yanhua Qu; Qisen Yang (Global Change Biology, 2025)
Climate change poses a severe threat to desert ecosystems; however, understanding how specialized desert species respond to changing climate remains limited. These species are confronting extreme changes, including intensified droughts, altered precipitation, and temperature patterns. Here, we integrate population and ecogenomic approaches to examine population genetic structure, demographic history, and climate adaptation in two distantly related, sympatric rodent species in arid and semi‐arid regions in East Asia. We further combine genomic offset analysis, ecological niche modeling, and landscape connectivity assessments to evaluate their climate change risks. Our results reveal that the two species have diverged into five geographically distinct lineages, each associated with a different arid region. Lineage divergence times are estimated between 20 and 400 thousand years ago, with population size declines occurring around the Last Glacial Maximum. While the two species exhibited distinct climate adaptation, evidenced by different key climatic variables and associated genes identified for each species, they exhibited congruent vulnerability to future climate change. This was indicated by parallel patterns of genomic offset and niche suitability loss. Under future climate change scenarios, eastern lineages in high precipitation seasonality areas (e.g., DB lineages in Horqin Sandy Land) face a higher risk due to substantial genomic offset, habitat loss, and reduced connectivity. In contrast, lineages on the west ranges with low precipitation seasonality (e.g., QH lineages in the Qaidam Basin and HL lineage in the Changtang Plateau) appear less vulnerable, characterized by lower genomic offset and the expansion of desert habitats. Overall, this study provides a comprehensive framework for identifying vulnerable populations and predicting responses to climate changes in desert species, offering critical insights for the conservation of desert ecosystems.

Hydrophilicity-dependent photodegradation of antibiotics in ice: Freeze-concentration effects and dissolved organic matter interactions drive divergent kinetics, pathways and toxicity - Jingshuang Cui; Yue Chen; Fangyuan Cheng; Hao Yang; Jiao Qu; Ya-nan Zhang; Willie J.G.M. Peijnenburg (Water Research, 2025)

Visible light-mediated persulfate activation by magnetite: Wavelength-specific radical generation and bisphenol AF transformation pathways - Ying Zhang; Cheng Qin; Jiajia Pang; Xiaoxue Pan; Rehab Khaled Mahmoud; Xiaosheng Tang; Zunyao Wang; Ruijuan Qu (Science of The Total Environment, 2025)

Ensemble atomic sites for acidic oxygen evolution: mechanisms, atomic engineering, and AI-assisted screening - Wenjia Qu; Xingen Lin; Handuo Zheng; Jianuo Liu; Cheng Qian; Kong Chen; Huang Zhou; Yafei Zhao; Quan-Hong Yang; Yuen Wu (Science Bulletin, 2025)

Mechanism of dual-pathway peroxymonosulfate activation via Co-Nx coordination-regulated broad-pH-adaptive carbon aerogel for ciprofloxacin degradation - Linjin Li; Jun Wang; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Junyan Li; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Xiaofei Li; et al. (Environmental Research, 2025)

Effects of copper and zinc on three stages-anaerobic fermentation of organic wastes - Yingying Cai; Minhua Cheng; Xinxin Liu; Guangfei Qu; Hongmei Zou; Heng Li; Shiqiang Zhao; Nanqi Ren (Environmental Research, 2025)

Effects and mechanisms of MSCs and MSC-derived exosomes in regulating ferroptosis - Zhiliang Guo; Zhuojian Qu; Yubing Zhang; Donghua Xu; Lijuan Chu; Min Cheng (Journal of Physiology and Biochemistry, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Quantitative probe detection of photosensitized dibromide radical anions generated from dissolved organic matter in aquatic systems - Fangyuan Cheng; Tingting Zhang; Hao Yang; Jiao Qu; Weihua Song; Ya-nan Zhang (Water Research, 2025)

Single and combined brominated flame retardants exposures are associated with sex steroid hormones in US adults: NHANES 2013–2016 analysis - Guan Cheng; Jiahui Wen; Feng Zhang; Rui Qu; Zhimin Deng; Fangfang Dai; Yanfei Xiao; Mengyang Dai; Tailang Yin; Jie Yan; Yan Zhang (Reproductive Toxicology, 2025)

Predictive modeling and mechanistic interpretation of single electron transfer reactivity between antibiotics and reactive halogen species - Linlin Dong; Chenxuan Zong; Jiao Qu; Fangyuan Cheng; Ya-nan Zhang (Journal of Hazardous Materials, 2025)

Manipulating internal catalytic microenvironment of dynamic Cu/SSZ-13 catalysts by in situ Ce incorporation for efficient NH3-SCR - Yan Wang; Tiantian Zhang; Xinya Wu; Yuanjiang Wang; Hao Qu; Cheng Zhang; Jianguo Cui; Cailing Xu; Zhaoqiang Li; Yongquan Qu; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2025)

Regulation of AMPs expression by six Tolls in stomach during WSSV infection in Macrobrachium nipponense - Qian Ren; Ying Huang; Chen Qu; Cheng-Xiang Zhou (Fish & Shellfish Immunology, 2025)

Multi-omics integration reveals gut Microbiome and Short-chain fatty acid profiles in gastric cancer cachexia patients and their clinical significance - Hao Liu; Yuxi Cheng; Shanjun Tan; Yidan Qu; Zhige Zhang; Mingyue Yan; Guohao Wu (World Journal of Microbiology and Biotechnology, 2025)

Therapeutic potential of Angelica sinensis derivatized carbon dots in ameliorating chemotherapy-induced anemia - Ruolan Kong; Yujiao Yuan; Jiaxing Liu; Kai Cheng; Yifan Zhang; Xiwen Zhang; Peng Zou; Yan Huang; Jinyu Ma; Chenxin He; Hui Kong; Yan Zhao; et al. (Journal of Molecular Histology, 2025)

Improvement of isolation and drug testing methods for Corynebacterium spp. in clinical specimens of granulomatous mastitis - Fang Liu; Yewei Yuan; Ruiyang Wu; Ninghua Tang; Kehua Chen; Kui Fan; Wei Cheng; Qu Pan (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Analysis of the shallow water bathymetric accuracy of ICESat-2 in combination with marine environmental factors - Sensen Chu; Ruihan Xu; Xuedong Zhang; Jian Cheng; Jizhe Li; Qixin Hu; Li Ye; Ziyang Qu (Marine Geodesy, 2025)

Hyperspectral Satellite-Derived Bathymetry Considering Substrate Characteristics - Li Ye; Sensen Chu; Hui Chen; Jian Cheng; Ruihan Xu; Ziyang Qu (Marine Geodesy, 2025)

CDIP-ChatGLM3: A dual-model approach integrating computer vision and language modeling for crop disease identification and prescription - Changqing Yan; Zeyun Liang; Han Cheng; Shuyang Li; Guangpeng Yang; Zhiwei Li; Ling Yin; Junjie Qu; Jing Wang; Genghong Wu; Qi Tian; Qiang Yu; et al. (Computers and Electronics in Agriculture, 2025)

LP-01 Sub-chronic Immune toxicity of inhaled black phosphorus nanosheets in mice - J. Cheng; G. Qu (Toxicology Letters, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Distribution patterns and ecological risks of antibiotic resistance genes in the Yap Trench - Jianxing Sun; Yuan-Guo Xie; Hongbo Zhou; Lei Chen; Yan-Ni Qu; Haina Cheng; Zhu Chen; Zheng-Shuang Hua; Yuguang Wang (Water Research, 2025)

Unveiling the urban form-environment relationship: Assessing the impact of urban shrinkage on carbon productivity in China - Leshui Zhang; Yanbo Qu; Kaiming Cheng (Urban Climate, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Non-negligible effects of sunlight irradiation on generation of VBNC-state antibiotic resistant bacteria in natural water - Tingting Zhang; Fangyuan Cheng; Linyi Fan; Ya-nan Zhang; Jiao Qu; Willie J.G.M. Peijnenburg (Journal of Hazardous Materials, 2025)

Biological fitness of an oligophagous herbivore Chrysomela populi on two different poplars - Yujia Cheng; Ziqi Qu; Sufang Zhang; Fu Liu; Xiangbo Kong; Tingbo Jiang; Jiaxing Fang (Journal of Insect Physiology, 2025)

A new type of carbonaceous reducing agent pellets for industrial silicon smelting with low grade non-stick coal coupled micro-silicon powder: from laboratory scale to industrial test scale - Xiaowei Gan; Zhengjie Chen; Wenhui Ma; Xiaowei Chen; Junyu Qu; Yaopan Hu; Jianhua Wen; Zening Cheng (Journal of Cleaner Production, 2025)

Global potential for regime shifts among shrubland, grassland, and forest - Zhuoran Qu; Xiaoyan Li; Sha Zhou; Yuanhong Deng; Chao Yang; Fangzhong Shi; Linhai Cheng (Global and Planetary Change, 2025)

Insights into the enhancement of Copper-Lanthanum interactions on the potassium tolerance of Cu/La-SSZ-13 for NH3-SCR - Na Kang; Yuanjiang Wang; Jiebing He; Yan Wang; Xin Guo; Hao Qu; Taintian Zhang; Cheng Zhang; Mi Yan; Pengfei Xie (Chemical Engineering Journal, 2025)

Exposure to the prenatal enriched environment alters maternal gut microbiota and promotes embryonic neurodevelopment via activating the AHR-Src pathway - Yuhan Liu; Chenna Huang; Xuejun Cheng; Wenzheng Qu; Xueyi Wang; Suxiao Liu; Jinyu Zhang; Ying Li; Xiaoli Huang; Jinpiao Zhu; Daqing Ma; Qiang Shu; et al. (Science China Life Sciences, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

GAIN: A long-term maize germplasm innovation plan - Yang Wang; Peng Zhang; Yingjie Xiao; Hai-Jun Liu; Junqiang Ding; Yanzhi Qu; Jionghao Gao; Wenlong Li; Xiangyang Guo; Angui Wang; Wenqiang Li; Gengshen Chen; et al. (Molecular Plant, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

Efficient fabrication of hunting trap-inspired degradable film with enhancing antimicrobial activity and reducing fomite transmission - Yu Du; Kai Mu; Xiaolong Li; Cheng Li; Chao Ding; Pingxu Chen; Ting Wu; Heng Xie; Jinping Qu (Journal of Hazardous Materials, 2025)

Antibiotic resistance gene transfer characteristic and risk evaluation: The entire process from swine manure to biogas slurry and then to soil - Pengcheng Liang; Hu Wang; Quanxu Chen; Qu Luo; Jianbo Cheng; Guangliang Tian; Tengbing He; Wenhai Zhu; Tianling Fu (Journal of Environmental Chemical Engineering, 2025)

Dihydroxy functionalized binuclear carbonate based poly(ionic liquid)s for highly efficient conversion of low-concentration CO2 into cyclic carbonate - Yuqiao Jiang; Xinyu Yuan; Peiru Wang; Linyan Cheng; Ranran Li; Qinghua Qu; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2025)

Advanced materials for CO2 capture and storage: A comprehensive review of current progress and future prospects - Jun Wang; Linjin Li; Guangfei Qu; Minhua Cheng; Yuanchuan Ren; Ping Lu; Ting Zhang; Yaoze Wang; Fenghui Wu (Journal of Environmental Chemical Engineering, 2025)

Promotional activity of an uncharacterized protein Bm0979 on Nosema bombycis in silkworm, bombyx mori - Yujia Fang; Qiong Yu; Wenzhe Chen; Zhenghao Han; Qingsheng Qu; Zhenwei Jia; Shidong Jiang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Asia-Pacific Entomology, 2025)

Determination of the spatiotemporal evolution patterns and obstacle factors of coupling coordination of the water–energy–food–ecology system in Ordos City, China - Jihong Qu; Jixian Lin; Mengting Cheng; Zezhong Zhang; Kai Feng; Fei Wang; Kun Ren; Juan Zhou; Yanbin Li (Environmental Geochemistry and Health, 2025)

Attention-guided multi-task network for streak-like dim and small space target detection in single optical images - Falin Wu; Haoxin Li; Guoxin Qu; Chunxiao Zhang; Yushuang Liu; Jingyao Yang; Dongjing Yang; Yuting Cheng (Advances in Space Research, 2025)

Self-supported bimetallic selenide heterostructure catalyst with enhanced electronic interaction for industrial-level seawater electrolysis - Yingwei Qi; Jiafu Chen; Di Liu; Xiaotian Wei; Lihang Qu; Cheng Huang; Kai Liu; Yaohai Cai; Dong Liu; Zhenbo Wang (Chemical Engineering Journal, 2025)

Insights into the Rooting and Growth-Promoting Effects of endophytic Fungus Serendipita indica in Blueberry (Vaccinium corymbosum) - Pengyan Qu; Zening Zhang; Ruide Li; Rui Liu; Yongyan Zhang; Chunzhen Cheng (Journal of Plant Growth Regulation, 2025)

Associations of urinary essential metals and their mixture with metabolic syndrome and its components among Chinese community-dwelling older adults - Panpan Wang; Xuqiu Cheng; Chen Zhang; Jingyuan Lei; Hongli Wang; Yuan Wang; Liang Sun; Bing Hu; Guangbo Qu; Dongmei Zhang; Guimei Chen; Chunmei Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Quorum sensing-enhanced electron transfer in anammox consortia: A mechanism for improved resistance to variable-valence heavy metals - Caiyan Qu; Jiong Tang; Jingyu Liu; Wenming Wang; Fengming Song; Siyuan Cheng; Xi Tang; Chong-Jian Tang (Journal of Hazardous Materials, 2025)

The three-dimensional electrocatalytic oxidation system for refractory organic wastewater remediations: Mechanisms, electrode material and applications - Linjin Li; Yaoze Wang; Guangfei Qu; Ping Lu; Ting Zhang; Jun Wang; Minhua Cheng; Nanqi Ren; Yuanchuan Ren (Journal of Environmental Chemical Engineering, 2025)

RNA Binding Protein IGF2BP3 Rehabilitates Glycolysis of Vascular Endothelial Cells to Protect the ox-LDL-induced Cellular Injury via Stabilizing LDHA mRNA - Xing-Chun Mo; Ping Lu; Qu-Cheng Wei; Xiao-Jing Yang (Cell Biochemistry and Biophysics, 2025)

Mechanisms and Enhancement of Hydrogen Evolution for Membrane Anti-fouling and Methane Upgrading by Sacrificed Anode in a Novel Electro-AnMBR - Jinzhou Fan; Zhibin Chen; Yu Cheng; He Ji; Chengzhi Hu; Jiuhui Qu (Water Research, 2025)

How do external uncertainties impact connectedness among carbon, fossil and clean energy markets? An analysis of extreme risk - Lei Cheng; Rui-Xiang Qiu; Lu-Tao Zhao; Zhi Qu (Journal of Cleaner Production, 2025)

High-performance and short-process sulphur autotrophic denitrification from low-C/N wastewater using novel suspended bio-S0 filters - Rashmi Koju; Yu Cheng; Shujia Gao; Tista Prasai Joshi; Chengzhi Hu; Min Yang; Jiuhui Qu (Journal of Cleaner Production, 2025)

Differences in microbial communities and phosphorus cycles between rural and urban lakes: Based on glyphosate and AMPA effects - Xuan Cheng; Mengjie Qu; Yang Hu; Xingyu Liu; Yunjun Mei (Journal of Environmental Management, 2025)

Characterization of microplastic distribution, sources and potential ecological risk assessment of domestic sewage from ships - Na Lu; Qing Su; Yuxia Li; Ling Qu; Lingna Kong; Jiayi Cheng; Chao Wang; Jian Sun; Jianbo Han; Xiaomeng Wang (Environmental Research, 2025)

Distribution characteristics of microplastics in surface waters in the western Pacific Ocean - Cheng Huo; Shoufeng Zhang; Ling Qu; Shuaichen Jin; Cijia Wang; Xiaoting Chu; Maowei Ju (Journal of Oceanology and Limnology, 2025)

Characteristics and predictions of accumulative deformation of structured soft soil under long-term cyclic loading - Weizheng Liu; Jiming Tan; Weihua Lv; Cheng Chen; Shuai Qu (Soil Dynamics and Earthquake Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Piezoelectric polarization-induced photogenerated carriers transfer coupled with active electron transport Z-scheme heterojunction synergistic optimization of BiFeO3/CdS composite photocatalysts for hydrogen production - Xinyu Ma; Rui Li; Zhao Li; Long Zhang; Yongjie Cao; Kui Nie; Die Zhou; Qing Ji; Cheng Wang; Zehua Zhang; Yutian Li; Meidan Que; et al. (Journal of Environmental Chemical Engineering, 2025)

Sedimentary responses to climatic variations and Kuroshio intrusion into the northern South China Sea since the last deglaciation - Chao Huang; Liyuan Wu; Jiansen Cheng; Xiaoxu Qu; Yongyi Luo; Huiling Zhang; Feng Ye; Gangjian Wei (Global and Planetary Change, 2025)

Immuno- and gut microbiota-modulatory activities of β-1,6-glucans from Lentinus edodes - Xian Qu; Yahui Ji; Jieyi Long; Donglin Zheng; Zhonghui Qiao; Yue Lin; Chang Lu; Yifa Zhou; Hairong Cheng (Food Chemistry, 2025)

Bimetallic coreshell nanorods with thioglycolic acid monolayer for highly sensitive and rapid SERS detection of thiabendazole and ziram residues in Prunus Persica peaches - Nisar Hussain; Yuzhu Li; Cheng Qu; Ning Li; Honglin Liu (Food Chemistry, 2025)

Enzymatic synthesis of structured phospholipids with ideal ω-6/3 fatty acid ratios via supplementation with α-linolenic acid from silkworm pupae oil - Lu Tan; Jin-Zheng Wang; Xin-Ying Wang; Cheng-Hai Yan; Ya-Xin Qu; Ze-Lai Huang; Tao Bai; Jun-Feng Qian; Jun Wang (Food Bioscience, 2025)

Mechanical properties of a novel fiber-bridging interface for connecting FRP profile and concrete - Hongwei Lin; Haidong Qu; Peng Feng; Huixin Zeng; Guanzhi Cheng (Engineering Structures, 2025)

Corrigendum to “Mechanism of charge self-reversal nano-nutrient delivery system to overcome the mucosal barrier” [Chem. Eng. J. 499 (2024) 155594] - Yaqing Bian; Tongliang Yang; Zihan Qu; Tiantian Zhang; Cheng Yang; Guiyun Chen; Ye Chen; Shuhong Li (Chemical Engineering Journal, 2025)

Large-Scale synthesis of crystalline phosphorus nanosheets with superior air-water stability and flame-retardancy ability - Zunbin Duan; Rui Li; He Bian; Yanfang Wang; Xue Zhang; Ziqiang Cheng; Danni Liu; Yang Li; Shuai Zhang; Guangbo Qu; Paul K. Chu; Jiahong Wang (Chemical Engineering Journal, 2025)

Mechanism of chlorobenzene removal in biotrickling filter enhanced by non-thermal plasma: Insights from biodiversity and functional gene perspectives - Miaomiao Qu; Yi Zheng; Zhuowei Cheng; Yun Shi; Wenjun Wang; Xiaoming Wu; Jianmeng Chen (Bioresource Technology, 2025)

Dehydration, heavy metal removal patterns, and microbial response in high moisture copper-containing sludge composting assisted by electromagnetic techniques - X. Chu; G. Qu; H. Zou; M. Cheng; J. Li; N. Ren (International Journal of Environmental Science and Technology, 2025)

A study on the stability of dangerous rock mass under blasting vibration considering size effect - Xinggen Chen; Xinyu Qu; Hongtao Li; Cheng Li; Gongda Lu; Qiang Yao (Bulletin of Engineering Geology and the Environment, 2025)

Sublethal and transgenerational effects of tetraniliprole on the tomato pinworm Phthorimaea (=Tuta) absoluta (Lepidoptera: Gelechiidae) - Jiaqi Yao; Cheng Qu; Yunyi Li; Yuguang Wang; Chen Luo; Raul Narciso C. Guedes; Ran Wang (Crop Protection, 2025)

Assessing lead fraction derived from passive microwave images and improving estimates at pixel-wise level - Xi Zhao; Jiaxing Gong; Meng Qu; Lijuan Song; Xiao Cheng (Remote Sensing of Environment, 2025)

Simulation study on the effect of temperature on hydrogen production performance of alkaline electrolytic water - Xiaobing Bi; Gan Wang; Daan Cui; Xinyi Qu; Shuaishuai Shi; Dong Yu; Mojie Cheng; Yulong Ji (Fuel, 2025)

Preparation of high quality carbon nanotubes by catalytic pyrolysis of waste plastics using FeNi-based catalyst - Weibo Meng; Baolin Xing; Song Cheng; Yanhe Nie; Huihui Zeng; Xiaoxiao Qu; Bing Xu; Chuanxiang Zhang; Jianglong Yu; Suck Won Hong (Waste Management, 2024)

Seismic retrofitting of GFRP-reinforced concrete columns using precast UHPC plates - Cheng Wu; Gao Ma; Deju Zhu; Hongya Qu; Haiyang Zhuang (Soil Dynamics and Earthquake Engineering, 2024)

Effect of steady boundary-layer flow on the hydrodynamic forces on a near-wall cylinder in currents - Yunfei Teng; Terry Griffiths; Liang Cheng; Yan Qu; Hongwei An; Scott Draper; Zhe Gao; Guoqiang Tang; Lin Lu (Ocean Engineering, 2024)

Relationship of CO2 adsorption performance and physicochemical property of biochar prepared by different types of biomass waste - Yuanyuan Zhang; Mengqing Qu; Jingkuan Li; Lei Ren; Fei Wang; Jing Wang; Fengling Yang; Fangqin Cheng (Journal of Environmental Chemical Engineering, 2024)

Machine learning-guided engineering of phosphocholine cytidylyltransferase for improved activity and halotolerance in citicoline production - Qingshi Wen; Cheng Zheng; Rongxin Miao; Mingjin Qu; Hanjie Ying; Junzhi Wang (Food Bioscience, 2024)

A study on the synergistic interaction of pea protein isolate and whey protein isolate for enhancing the stability and quality of krill oil emulsion - Danping Jin; Yuping Qu; Weibo Lu; Lijun Ge; Haifeng Wang; Jing Xue; Dan Deng; Qiong Zhang; Keyun Cheng; Huijuan Yang; Qing Shen (Food Hydrocolloids, 2024)

Effect of dynamic high-pressure microfluidization and thermal processing on quality and volatile components of NFC tomato juice - Zhiwei Zhang; Shuaixue Mu; Zhenhong Gao; Xinyi Yang; Meiyue Zhang; Yuying Cheng; Kunsheng Qu (Food and Bioproducts Processing, 2024)

Co-toxicity and co-contamination remediation of polycyclic aromatic hydrocarbons and heavy metals: Research progress and future perspectives - Xiyao Qu; Qiuya Niu; Cheng Sheng; Mengmeng Xia; Chengxu Zhang; Xiaolin Qu; Chunping Yang (Environmental Research, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

Enhancing microfiltration membrane performance by sodium percarbonate-based oxidation for hydraulic fracturing wastewater treatment - Haiqing Chang; Yingyuan Zhu; Naiming Liu; Pengwei Ji; Zhongsen Yan; Xiaoxiang Cheng; Dan Qu; Heng Liang; Fangshu Qu (Environmental Research, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Adsorption and migration behaviors of heavy metals (As, Cd, and Cr) in single and binary systems in typical Chinese soils - Wenqian Cao; Cheng Qin; Ying Zhang; Junyan Wei; Asam Shad; Ruijuan Qu; Qiming Xian; Zunyao Wang (Science of The Total Environment, 2024)

Resistance monitoring of diamide insecticides and characterization of field-evolved chlorantraniliprole resistance among Chinese populations of the tomato pinworm Phthorimaea (=Tuta) absoluta (Lepidoptera: Gelechiidae) - Xiaoli Ma; Cheng Qu; Jiaqi Yao; Jixing Xia; Chen Luo; Raul Narciso C. Guedes; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

Experimental study on the influence of particle morphology on compression characteristics of coral sand in South China Sea - Ru Qu; Cheng-hao Ma; Chang-qi Zhu; Hai-feng Liu (Ocean Engineering, 2024)

Experimental investigation on the hydrodynamic performance of a bioinspired manta-ray underwater vehicle in various forward propulsion modes - Cheng Xing; Zhonghua Yin; Hanxuan Xu; Yonghui Cao; Yilin Qu; Qiaogao Huang; Guang Pan; Yong Cao (Ocean Engineering, 2024)

A multi-scale mixed information-driven hybrid deep neural network model for predicting unsteady flows - Zhicheng Gong; Zili Xu; Shizhi Zhao; Lu Cheng; Jiangji Qu; Yu Fang (Ocean Engineering, 2024)

Copper-based photocatalysts with natural organic ligands for efficient removal of tetracycline under visible light - Shouxin Zhu; Can Sun; Zhexiao Zhu; Jingyi Qu; Zijie Fang; Yangben Chen; Jiahui Lin; Xiaolu Xu; Miaoyan Cheng; Min Jiang; Hui Zheng (Journal of Environmental Management, 2024)

Spontaneous imbibition in hydrate-bearing sediments under creep - Kailun Wang; Gang Lei; Jiangtao Qu; Yang Wu; Wan Cheng; Jiadi Tang; Yuyi Lu (Gas Science and Engineering, 2024)

How do glyphosate and AMPA alter the microbial community structure and phosphorus cycle in rice-crayfish systems? - Mengjie Qu; Xuan Cheng; Qiang Xu; Yang Hu; Xingyu Liu; Yunjun Mei (Environmental Research, 2024)

Comprehensive analysis and risk assessment of Antibiotic contaminants, antibiotic-resistant bacteria, and resistance genes: Patterns, drivers, and implications in the Songliao Basin - Anjie Chen; Tingting Zhang; Fangyuan Cheng; Hao Yang; Zhengfeng Guo; Siyu Zhao; Ya-nan Zhang; Jiao Qu (Environmental Pollution, 2024)

Mechanism of charge self-reversal nano-nutrient delivery system to overcome the mucosal barrier - Yaqing Bian; Tongliang Yang; Zihan Qu; Tiantian Zhang; Cheng Yang; Guiyun Chen; Ye Chen; Shuhong Li (Chemical Engineering Journal, 2024)

Amentoflavone alleviated cartilage injury and inflammatory response of knee osteoarthritis through PTGS2 - Yiheng Cheng; Xiaofeng Liu; Wenqing Qu; Xin Wang; Hao Su; Wenliang Li; Wenqiang Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Research on the conversion of biowaste to MCCAs: A review of recent advances in the electrochemical synergistic anaerobic pathway - Minhua Cheng; Guangfei Qu; Rui Xu; Nanqi Ren (Chemosphere, 2024)

Real-time tilapia fillet defect segmentation on edge device for robotic trimming - Yingchao He; Weidong Xu; Da Liu; Maozhen Qu; Jiaying Fu; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Acid-base neutralization strategy for immobilization amino acid ionic liquid within sulfonic acid-based COF as a switch for selective conversion of epoxides - Qingyuan Xue; Linyan Cheng; Qinghua Qu; Lingwei Yang; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Array-optimized artificial olfactory sensor enabling cost-effective and non-destructive detection of mycotoxin-contaminated maize - Maozhen Qu; Yingchao He; Weidong Xu; Da Liu; Changqing An; Shanming Liu; Guang Liu; Fang Cheng (Food Chemistry, 2024)

Research on the method of determining landslide threshold based on accelerating point dynamic identification - Xinmin Hou; Yifan Liu; Jiangbo Xu; Zhanhui Qu; Fanghui Cheng; Shaohua Chen; Xuzhen Zhang (Landslides, 2024)

Risk assessment, cross-resistance, biochemical mechanism and fitness cost of tetraniliprole resistance in the tomato pinworm Tuta absoluta - Cheng Qu; Jiaqi Yao; Qianyuan Zhan; Daofeng Zhang; Yunyi Li; Jianlei Huang; Ran Wang (Crop Protection, 2024)

Distribution characteristics and ecological risk analysis of microplastics in sediments and effluents related to offshore oil and gas activities in the Bohai Sea, China - Yuxia Li; Lingna Kong; Zhongxiu Li; Qing Su; Ling Qu; Xiaomeng Wang; Jianbo Han; Jiayi Cheng; Liang Wu; Naidong Zhang (Marine Pollution Bulletin, 2024)

Cytotoxic xanthanolide sesquiterpenes from the fruits of Xanthium italicum Moretti - Yu-Tong Li; Cheng-Yong Tan; Jiang Fu; Hai-Qiang Wang; Yun-Bao Liu; Shuang-Gang Ma; Yong Li; Jing Qu; Shi-Shan Yu (Phytochemistry, 2024)

Tetraniliprole risk assessment: Unveiling a hidden threat for managing a generalist herbivore - Cheng Qu; Yunyi Li; Qianyuan Zhan; Jinda Wang; Chen Luo; Raul Narciso C. Guedes; Ran Wang (Environmental Research, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

Pharmacokinetics and safety of a new generic lurasidone: a phase I bioequivalence study in healthy Chinese subjects - Zhengzhi Liu; Jinling Xue; Qiaohuan Deng; Yanli Wang; Lixiu Zhang; Lang Liu; Nan Xiao; Tianying Chang; Yingzi Cui; Yang Cheng; Guangwen Liu; Wanhua Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Assessing the causal relationship between immune cells and prostatitis: evidence from bidirectional mendelian randomization analysis - Genyi Qu; Weimin Jiang; Zhaohui Long; Xing Zhou; Yijie Wang; Guang Yang; Cheng Tang; Yong Xu (Mammalian Genome, 2024)

Recent advances in hydrogen process safety: Deflagration behaviors and explosion mitigation strategies - Peng Yang; Tao Wang; Yuhuai Sheng; Yingying Yu; Ruikang Li; Bin Su; Fangming Cheng; Jiao Qu; Jun Deng; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

Tetraniliprole resistance in field-collected populations of Tuta absoluta (Lepidoptera: Gelechiidae) from China: Baseline susceptibility, cross-resistance, inheritance, and biochemical mechanism - Cheng Qu; Jiaqi Yao; Jianlei Huang; Wunan Che; Yong Fang; Chen Luo; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

Baseline of susceptibility, risk assessment, biochemical mechanism, and fitness cost of resistance to dimpropyridaz, a novel pyridazine pyrazolecarboxamide insecticide, in Bemisia tabaci from China - Juan Tang; Cheng Qu; Qianyuan Zhan; Daofeng Zhang; Jinda Wang; Chen Luo; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

Lifetime assessment of deep-sea manned cabin with PMMA pressure-resistant hull prior to micro-cracks - Zhihao He; Fang Wang; Oleg Gaidai; Wenxin Qu; Cheng Li (Ocean Engineering, 2024)

Enhancing the stability of zein pickering foams via hydrophilic reassembly with sugar alcohols and glycosides: A structural and molecular investigation - Zihan Qu; Guiyun Chen; Tongliang Yang; Fushen Niu; Yaqing Bian; Cheng Yang; Ye Chen; Shuhong Li (Food Hydrocolloids, 2024)

Numerical simulation of fracture propagation morphology in hydraulic fracturing development of geothermal reservoirs based on the CDEM-THM3D - Wang Jiwei; Guo Tiankui; Chen Ming; Qu Zhanqing; Zhang Bo; Zhang Wei; Zhai Cheng; Zheng Peng (Computers and Geotechnics, 2024)

Hybrid cell membranes camouflaged copper-loaded nano-prodrug for tumor angiogenesis inhibition and cell cuproptosis - Xian Qin; Li Zhu; Xuan An; Cheng Zhang; Jiawei Li; Fei Yan; Wenjin Zhang; Kai Qu; Kun Zhang; Wei Wu; Guicheng Wu (Chemical Engineering Journal, 2024)

Impact of the COVID-19 pandemic on daily travel: Findings from New South Wales, Australia - Bo Du; Cheng Zhang; Tianyang Qu; Qi Wang; Quan Spring Zhou; Tingru Cui; Pascal Perez; Thomas Astell-Burt (Travel Behaviour and Society, 2024)

Single-atom Al precisely modulate the strain of Pt3Co intermetallic for superior oxygen catalytic performance - Wei Wu; Wei Qu; Zichen Wang; Yangyang Tan; Runzhe Chen; Suhao Chen; Haifeng Lv; Jun Zhong; Niancai Cheng (Chemical Engineering Journal, 2024)

Fucosyltransferase 8 regulates adult neurogenesis and cognition of mice by modulating the Itga6-PI3K/Akt signaling pathway - Hongfeng Guo; Qihang Sun; Xiaoli Huang; Xiaohao Wang; Feng Zhang; Wenzheng Qu; Jinling Liu; Xuejun Cheng; Qiang Zhu; Wen Yi; Qiang Shu; Xuekun Li (Science China Life Sciences, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Effect of initial moisture content, resulting from different ratios of vegetable waste to maize straw, on compost was mediated by composting temperatures and microbial communities at low temperatures - Shanshan Sun; Cheng Guo; Jianyu Wang; Li Ren; Jianping Qu; Qi Guan; Nongxiao Dou; Jiahui Zhang; Qiuhua Chen; Qi Wang; Jiguang Wang; Jieming Li; et al. (Chemosphere, 2024)

Absorption characteristics and molecular mechanism of a low viscosity iron-based ionic liquid for removing H2S - Zhonghao Li; Zhou Feng; Hongwei Jin; Kangkang Li; Hongzhi Xia; Shiqi Qu; Sujuan Ye; Huanong Cheng; Qingli Wei; Yugang Li; Xinshun Tan; Shiqing Zheng (Journal of Environmental Chemical Engineering, 2024)

Preparation of polystyrene and silane-modified nano-silica superhydrophobic and superoleophilic three-dimensional composite fiber membranes for efficient oil absorption and oil-water separation - Zhihui Dong; Nan Qu; Qiushi Jiang; Tong Zhang; Zhaolian Han; Jiapeng Li; Ruiqi Zhang; Zhiqiang Cheng (Journal of Environmental Chemical Engineering, 2024)

Deep learning network with new weighting strategy for ISAR image enhancement - Ping Cheng; Xinmiao Xu; Xinkai Yang; Yunqing Nie; Weiyang Chen; Zhiyu Qu; Jiaqun Zhao (International Journal of Remote Sensing, 2024)

Synchronous in-situ sludge reduction and enhanced denitrification through improving electron transfer during endogenous metabolisms with Fe(Ⅱ) addition - Yu Cheng; Chenghai Lu; Shujia Gao; Rashmi Koju; Haiyan Li; Zongqiang Zhu; Chengzhi Hu; Jiuhui Qu (Water Research, 2024)

Knockdown of one cytochrome P450 gene CYP6DW4 increases the susceptibility of Bemisia tabaci to dimpropyridaz, a novel pyridazine pyrazolecarboxamide insecticide - Juan Tang; Qinghe Zhang; Cheng Qu; Qi Su; Chen Luo; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

Investigating the influences of wind function parameterization on evaporation estimation using the generalized complementary principle - Xuxin Lei; Qu Li; Lei Cheng; Shujing Qin; Pan Liu; Lu Zhang (Journal of Hydrology, 2024)

Effects of dissolved organic matter and halogen ions on phototransformation of pharmaceuticals and personal care products in aquatic environments - Fangyuan Cheng; Tingting Zhang; Hao Yang; Yue Liu; Jiao Qu; Ya-nan Zhang; Willie J.G.M. Peijnenburg (Journal of Hazardous Materials, 2024)

Relationship between optical properties and internal quality of potatoes during storage - Zhengwei Xiao; Yingchao Xu; Xiangyou Wang; Yi Wang; Junzhe Qu; Meng Cheng; Shengfa Chen (Food Chemistry, 2024)

Plasmonic nanostar@metal organic frameworks as strong adsorber, enricher, and sensor for trace nanoplastics via surface-enhanced Raman spectroscopy - Xian Wang; Shanshan Du; Cheng Qu; Fanfan Yu; Liqin Zheng; Mengke Su; Honglin Liu; Bing Shao (Chemical Engineering Journal, 2024)

Potential of combined reactor and static composting applications for the removal of heavy metals and antibiotic resistance genes from chicken manure - Qu Luo; Hu Wang; Xiaoqing Lu; Can Wang; Ruiying Chen; Jianbo Cheng; Tengbing He; Tianling Fu (Journal of Environmental Management, 2024)

Enhanced degradation of bisphenol AF (BPAF) by visible light irradiated zero valent iron activated persulfate system - Cheng Qin; Yumeng Qi; Qing Zheng; Xiaolei Teng; Ahmed A. Allam; Ahmed Rady; Zunyao Wang; Ruijuan Qu (Journal of Environmental Chemical Engineering, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Current status of research on microbial electrocatalytic CH4 production for biogas upgrading and challenges - Xiaomei Chu; Yuanchuan Ren; Guangfei Qu; Nanqi Ren; Ruosong Xie; Minhua Cheng; Xiuping Chen; Zuoliang Wang; Yongheng Yuan (Journal of Environmental Chemical Engineering, 2024)

Ce enhanced low-temperature performance of Mn modified Cu-Beta zeolite catalyst for NH3-SCR - Xin Guo; Zhiyong Ding; Na Kang; Liu Yang; Yuanjiang Wang; Cheng Zhang; Zhaoqiang Li; Tiantian Zhang; Yan Wang; Yu Wang; Hao Qu (Fuel, 2024)

Ce-UiO-66-F4-based composites decorated with green carbon dots for universal adsorption of organic pollutants containing hydrogen bond donors and its application exploration - Maozhen Qu; Hengjie Yu; Yingchao He; Weidong Xu; Da Liu; Fang Cheng (Chemical Engineering Journal, 2024)

Polymer Binder-Free aqueous spinning of biomimetic CNT based hierarchical hollow fiber for structural and energy storage application - Shuxuan Qu; Dandan Yang; Ningxiao Gao; Panpan Xu; Xinrong Jiang; Kang Cheng; Munan Lu; Yuqiong Wang; Weibang Lyu; Zhiqiang Liang (Chemical Engineering Journal, 2024)

Exploring the antiviral potential of paeonol from medicinal plants: A promising strategy for controlling white spot syndrome virus - Cheng Chen; Chang-Shuai Liang; Xiang-Yu Qu; Peng-Fei Li; Xiao-Ping Tan; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Experimental investigation and numerical analysis on the confined deflagration behavior of methane-air mixtures within the suppression of typical haloalkanes - Tao Wang; Yuhuai Sheng; Yingying Yu; Fangming Cheng; Xuhan Ding; Jiao Qu; Jun Deng; Fan Nan; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

A Rigid-Flexible Coupling Dynamic Model for Robotic Manta with Flexible Pectoral Fins - Yilin Qu; Xiao Xie; Shucheng Zhang; Cheng Xing; Yong Cao; Yonghui Cao; Guang Pan; Baowei Song (Journal of Marine Science and Engineering, 2024)
The manta ray, exemplifying an agile swimming mode identified as the median and paired fin (MPF) mode, inspired the development of underwater robots. Robotic manta typically comprises a central rigid body and flexible pectoral fins. Flexible fins provide excellent maneuverability. However, due to the complexity of material mechanics and hydrodynamics, its dynamics are rarely studied, which is crucial for the advanced control of robotic manta (such as trajectory tracking, obstacle avoidance, etc.). In this paper, we develop a multibody dynamic model for our novel manta robot by introducing a pseudo-rigid body (PRB) model to consider passive deformation in the spanwise direction of the pectoral fins while avoiding intricate modeling. In addressing the rigid-flexible coupling dynamics between flexible fins and the actuation mechanism, we employ a sequential coupling technique commonly used in fluid-structure interaction (FSI) problems. Numerical examples are provided to validate the MPF mode and demonstrate the effectiveness of the dynamic model. We show that our model performs well in the rigid-flexible coupling analysis of the manta robot. In addition to the straight-swimming scenario, we elucidate the viability of tailoring turning gaits through systematic variations in input parameters. Moreover, compared with finite element and CFD methods, the PRB method has high computational efficiency in rigid-flexible coupling problems. Its potential for real-time computation opens up possibilities for future model-based control.

Persistent free radicals on biochar for its catalytic capability: A review - Xiaoqing Liu; Zhijie Chen; Shun Lu; Xingdong Shi; Fulin Qu; Dongle Cheng; Wei Wei; Ho Kyong Shon; Bing-Jie Ni (Water Research, 2024)

Orco mediates olfactory behavior and oviposition in the whitefly Bemisia tabaci - Fengqi Li; Jiahui Tian; Zhongjuan Di; Cheng Qu; Yuejun Fu; Shiyong Yang; Chen Luo (Pesticide Biochemistry and Physiology, 2024)

Rational construction Ag/LiF/sulfide rich protective layer for remarkably enhancing the stability of Li metal anodes - Caili Xu; Shu Zhang; Cheng Chen; Yunhui Lin; Bing Qu; Haiping Zhou; Mengqiang Wu (Chemical Engineering Journal, 2024)

Simultaneous removal of organic micropollutants and metals from water by a multifunctional β-cyclodextrin polymer-supported-polyaniline composite - Pin Wang; Guangyu An; Peter Jarvis; Wen Liu; Shunke Ding; Ruixin Qu; Zhanghan Li; Cheng Ye; Wenhai Chu (Chemical Engineering Journal, 2024)

Artificial nose of scalable plasmonic array gas sensor for Multi-Dimensional SERS recognition of volatile organic compounds - Cheng Qu; Hao Fang; Fanfan Yu; Jinai Chen; Mengke Su; Honglin Liu (Chemical Engineering Journal, 2024)

A highly selective and sensitive electrochemical sensor for tetracycline resistant genes detection based on the non-covalent interaction of graphene oxide and nucleobase - Yi Xing; Yanan Zhang; Xiaolin Zhu; Chengzhi Wang; Tingting Zhang; Fangyuan Cheng; Jiao Qu; Willie J.G.M. Peijnenburg (Science of The Total Environment, 2024)

Fate of glyphosate in lakes with varying trophic levels and its modification by root exudates of submerged macrophytes - Mengjie Qu; Xuan Cheng; Qiang Xu; Ziming Zeng; Mingming Zheng; Yunjun Mei; Jianwei Zhao; Guanglong Liu (Journal of Hazardous Materials, 2024)

Process optimization, energy consumption analysis, and environmental assessment of total CO2 capture from syngas based on [NEMH][Ac] protic ionic liquid - Zhou Feng; Ning Wang; Xiaohan Li; Zhonghao Li; Kangkang Li; Hongwei Jin; Shiqi Qu; Hongzhi Xia; Huanong Cheng; Xinshun Tan; Shiqing Zheng (International Journal of Greenhouse Gas Control, 2024)

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

Targeting PKM2 improves the gemcitabine sensitivity of intrahepatic cholangiocarcinoma cells via inhibiting β-catenin signaling pathway - Wenna Yu; Fuling Zeng; Yang Xiao; Liuyan Chen; Hengdong Qu; Jian Hong; Chen Qu; Guohua Cheng (Chemico-Biological Interactions, 2024)

Intensified denitrification in a fluidized-bed reactor with suspended sulfur autotrophic microbial fillers - Zhenao Gu; Zheying Liu; Yu Cheng; Zongqiang Zhu; Jiayu Tian; Chengzhi Hu; Jiuhui Qu (Bioresource Technology, 2024)

Effects of dissolved organic matter, pH and nutrient on ciprofloxacin bioaccumulation and toxicity in duckweed - Mengnan Shen; Yi Hu; Ke Zhao; Zhi Qu; Chen Lyu; Binshuo Liu; Ming Li; Xiaodan Bu; Chenyang Li; Shuang Zhong; Jie Cheng (Aquatic Toxicology, 2024)

TREM-2 Drives Development of Multiple Sclerosis by Promoting Pathogenic Th17 Polarization - Siying Qu; Shengfeng Hu; Huiting Xu; Yongjian Wu; Siqi Ming; Xiaoxia Zhan; Cheng Wang; Xi Huang (Neuroscience Bulletin, 2024)

The impact of climate change and human activities on the change in the net primary productivity of vegetation—taking Sichuan Province as an example - Tangrui Dai; Xiaoai Dai; Heng Lu; Tao He; Weile Li; Cheng Li; Shengqi Huang; Yiyang Huang; Chenbo Tong; Ge Qu; Yunfeng Shan; Shuneng Liang; et al. (Environmental Science and Pollution Research, 2023)

Electroacoustic performance online measurement under extreme pressure using an 11,000-m transceiver - Zhiguo Qu; Zhi Zhong; Dapeng Zou; Xinghui Cao; Mingguang Shan; Yongqiang Xie; Hui Cheng (Marine Georesources & Geotechnology, 2023)

Long-lived Cenozoic positive relief of the south-Eastern Tian Shan: Insights from provenance analyses of the northwestern Kuqa Depression sediments - Jialun Huang; Xiubin Lin; Kaixuan An; Hanlin Chen; Xiaogan Cheng; Yang Qu; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Zhuxin Chen; Lin Jiang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Mechanism study on a novel Cu/Fe co-catalyzed heterogeneous particle mediated activation of hydrogen peroxide for efficient degradation of cyanides - Xiuping Chen; Ting Zhang; Guangfei Qu; Yuanchuan Ren; Zuoliang Wang; Jun Wang; Ping Lu; Minhua Cheng; Xiaomei Chu (Journal of Water Process Engineering, 2023)

Improving permeability and fouling resistance of GO hydrophilic/hydrophobic Janus membrane by polyether amine crosslinking for membrane distillation of dye wastewater - Nan Sun; Yuqing Qu; Aniu Qian; Rongjie Li; Huazhang Zhao; Fangqin Cheng; Jianfeng Li (Journal of Environmental Chemical Engineering, 2023)

Identifying cadmium and lead co-accumulation from living rice blade spectrum - Shuangyin Zhang; Teng Fei; Yiyun Chen; Jiaxin Yang; Ran Qu; Jian Xu; Xiao Xiao; Xuejun Cheng; Zhongzheng Hu; Xuedong Zheng; Dengzhong Zhao (Environmental Pollution, 2023)

High fire safety thermal protective composite aerogel with efficient thermal insulation and reversible fire warning performance for firefighting clothing - Zhicai Yu; Yuhang Wan; Yi Qin; Qing jiang; Jin-Ping Guan; Xian-Wei Cheng; Xiaochun Wang; Shengnan Ouyang; Xueru Qu; Zhenyu Zhu; Jinfeng Wang; Hualing He (Chemical Engineering Journal, 2023)

Constructing solution-processable heavy metal platinum (II) complex with narrowband emission by integrating multiple resonance molecular system - Yu Feng; Xuming Zhuang; Yincai Xu; Jianan Xue; Cheng Qu; Qingyang Wang; Yu Liu; Yue Wang (Chemical Engineering Journal, 2023)

Spontaneous compartmentalization in chitosan - phytate - lignosulfonate microparticles by gas-shearing microfluidics - Qingli Qu; Long Chen; Weixia Cheng; Jules Muhire; Anquan Yang; Jing Wang; Min Xie; Xiaoli Zhang; Dan Huang; Ranhua Xiong; Dong Pei; Chaobo Huang (Chemical Engineering Journal, 2023)

Dual reinforced composite membranes from in-situ ionic crosslinked quaternized chitosan filled quaternized polyvinylidene fluoride nanofiber for alkaline direct methanol fuel cell - Ying Ou; Ting Qu; Fan Cheng; Haiyang Yang; Fuqiang Hu; Jie Wang; Hai Liu; Guoliang Liu; Sheng Wen; Chunli Gong (Carbohydrate Polymers, 2023)

Optical properties and Monte Carlo multi-layered simulation of potato skin and flesh tissues - Zhengwei Xiao; Yingchao Xu; Xiangyou Wang; Yi Wang; Meng Cheng; Shuwei Liu; Junzhe Qu (Postharvest Biology and Technology, 2023)

Reduced nitrogen fertilization from pre-flowering to pre-veraison alters phenolic profiles of Vitis vinifera L. Cv. Cabernet Gernischt wine of Yantai, China - Jianqiang Song; Ang Zhang; Fei Gao; Mingqing Li; Xianhua Zhao; Jie Zhang; Genjie Wang; Yuping Hou; Shiwei Cheng; Huige Qu; Shili Ruan; Jiming Li (Food Research International, 2023)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

Obeticholic acid alleviates intrauterine growth restriction induced by di-ethyl-hexyl phthalate in pregnant female mice by improving bile acid disorder - Fan Zhao; Lun Zhang; Mingchao Qu; Lu Ye; Jiayi Zhang; Yun Yu; Qianqian Huang; Cheng Zhang; Jianqing Wang (Environmental Science and Pollution Research, 2023)

Comparative Analysis of Hepatopancreas RNA-Seq of Juvenile Grass Carp (Ctenopharyngodon idella) Fed Different Starch Diets - Jingjing Zhang; Xue Guo; Zhen Han; Letian Qu; Teng Xia; Xiangning Chen; Jianhe Xu; Zhujin Ding; Chaoqing Wei; Hanliang Cheng (Fishes, 2023)
This study aimed to explore the effects of different starch source diets on the growth performance and hepatopancreas RNA-seq of grass carp. Juvenile grass carp (initial body weight of 39.4 ± 1.6 g) were fed diets containing 25% corn (CO), potato (PO), and wheat (WH) starch for 8 weeks, respectively. The weight gain ratio (WGR) was significantly lower, whereas the visceral somatic index (VSI) and feed conversion ratio (FCR) were significantly higher in the CO group than those in the PO and WH groups. These indicators did not significantly differ between the PO and WH groups. Hepatopancreas RNA-seq analysis showed that 536, 514, and 647 differentially expressed genes (DEGs) were screened out in the comparisons of PO vs. WH, PO vs. CO, and CO vs. WH. The DEGs were mainly enriched in the several known pathways involved in steroid biosynthesis, cell cycle, fatty acid metabolism, and fat digestion and absorption according to Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis. The major DEGs related to lipid and carbohydrate metabolism were analyzed, in which lipogenesis-related DEGs (fasn, acc1, scd1, elovl6, and me1), fat digestion and absorption-related DEGs (fabp7, apoa1, apoa4, and pla2), and glycometabolism-related DEGs (gk, g6pd, and pepck) were down-regulated in the PO group compared with those in the CO and WH groups. Conversely, steroid synthesis-related DEGs (hmgcs, fdft1, sqle, lss, cyp51, msmo1, nsdhl, ugt, cyp1b1, and cyp7a1) were up-regulated in the PO group. These results indicate that the long-term PO ingestion could modulate hepatic lipid metabolism by reducing fatty acid biosynthesis and increasing bile acid biosynthesis. PO may be healthier in contrast to CO alone, which may not be suitable as a starch source in grass carp diet.

Responses of applied voltages on the archaea microbial distribution in sludge digestion - Yingying Cai; Heng Li; Guangfei Qu; Yinghui Hu; Hongmei Zou; Shiqiang Zhao; Minhua Cheng; Xiaomei Chu; Nanqi Ren (Chemosphere, 2023)

Preparation of pyrolysis products by catalytic pyrolysis of poplar: Application of biochar in antibiotic wastewater treatment - Xiaojing Qin; Song Cheng; Baolin Xing; XiaoXaio Qu; Changliang Shi; Weibo Meng; Chuanxiang Zhang; Hongying Xia (Chemosphere, 2023)

Study on the mechanism of rapid degradation of Rhodamine B with Fe/Cu@antimony tailing nano catalytic particle electrode in a three dimensional electrochemical reactor - Yuanchuan Ren; Ping Lu; Guangfei Qu; Ping Ning; Nanqi Ren; Jun Wang; Fenghui Wu; Xiuping Chen; Zuoliang Wang; Ting Zhang; Minhua Cheng; Xiaomei Chu (Water Research, 2023)

Distributions of nonlinear dynamics, stress and fatigue damage along a steel catenary riser in current affected by top-end surge - Zhuang Kang; Shaojie Li; Cheng Zhang; Yan Qu; Gang Ma (Ocean Engineering, 2023)

Screening metal tellurides as cathode materials for Li-Te batteries - Yulin Wang; Liangzhu Zhang; Pengyang Qu; Cheng Lian; Kai Huang; Haiping Su; Honglai Liu (Chemical Engineering Journal, 2023)

Membrane fouling alleviation by combination of sodium percarbonate oxidation and coagulation during microfiltration of shale gas produced water - Haiqing Chang; Naiming Liu; Fangshu Qu; Xiaoxiang Cheng; Zhiwei Zhou; Ying Liang; Ying Yu; Heng Liang (Chemical Engineering Journal, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

Late Carboniferous bimodal volcanic rocks of the West Junggar Terrane, NW China: Implications for the postcollisional tectonic setting of the southwestern CAOB - Xi Wang; Ran Wang; Pan Qu; Sanyou Cheng; Yonghui Xin (International Geology Review, 2023)

CO2 sequestration and CaCO3 recovery with steel slag by a novel two-step leaching and carbonation method - Can Cheng; Wenjun Huang; Haomiao Xu; Zhisong Liu; Xianwei Li; Hongzhi Shi; Yongmei Yu; Zan Qu; Naiqiang Yan (Science of The Total Environment, 2023)

Determination of excited triplet states of dissolved organic matter using chemical probes: A comparative and mechanistic study - Yue Liu; Fangyuan Cheng; Tingting Zhang; Jiao Qu; Ya-nan Zhang; Willie J.G.M. Peijnenburg (Journal of Hazardous Materials, 2023)

Air quality improvement assessment and exposure risk of Shandong Province in China during 2014 to 2020 - N. N. Wang; C. Y. Zhu; Wei Li; M. Y. Qiu; B. L. Wang; X. Y. Li; B. D. Jiang; X. Y. Qu; Z. S. Li; H. C. Cheng (International Journal of Environmental Science and Technology, 2023)

Seasonal distribution of microplastics in the surface waters of the Yellow Sea, China - Weiwei Zhang; Shoufeng Zhang; Ling Qu; Maowei Ju; Cheng Huo; Juying Wang (Marine Pollution Bulletin, 2023)

Pine pollen: A review of its chemical composition, health effects, processing, and food applications - Yong Cheng; Zhenyu Wang; Wei Quan; Chaoyi Xue; Tao Qu; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Fang Qin; Jie Chen; Zhiyong He (Trends in Food Science & Technology, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Identification of driving factors of lignocellulose degrading enzyme genes in different microbial communities during rice straw composting - Fengting Qu; Hanpeng Cheng; Ziyi Han; Zimin Wei; Caihong Song (Bioresource Technology, 2023)

The Effect of Short-Term Air Pollutants Exposure on Daily Mortality Among Elderly Individuals in China: A Systematic Review and Meta-Analysis - Cong Liu; Fengwei Jia; Mengmeng Ji; Guofeng Qu; Chunping Ye; Jiali Cheng; Andiara Schwingel; Rong Gao (Water, Air, & Soil Pollution, 2023)
To systematically review the literature regarding the effect of air pollutants on the excess mortality risk among the elderly Chinese. PubMed, Scopus, Web of Science (WOS), and Chinese National Knowledge Infrastructure (CNKI) electronic databases were searched. A standardized data extraction form was used to collect methodological and outcome variables from each eligible study. The effect value was combined with a fixed- or random-effect model, and sensitivity analysis and publication bias test were performed. A total of 26 articles on air pollutants and excess risk (ER) of mortality in the Chinese elderly were identified. Among them, 16, 14, 8, and 8 articles contained PM 2.5 , PM 10 , SO 2 , and NO 2 data, respectively. The meta-analysis results showed that the excess risk of mortality in the Chinese elderly associated with per 10 µg/m 3 increase in PM 2.5 , PM 10 , SO 2 , and NO 2 concentrations was 1.01%, 0.54%, 1.06%and 1.35%, respectively. Sufficient evidence supports that the increase in air pollutants (PM 2.5 , PM 10 , SO 2 , and NO 2 ) will escalate the mortality of the elderly in China. Future research can study two or more air pollution models and the impact of air pollution on elderly mortality rates under different temperatures, duration of exposure, seasons and regions.

Interannual variation of midsummer precipitation in the middle reaches of Yarlung Zangbo River and its possible mechanisms - Cheng Yang; Qu Chi; Shunwu Zhou; Ping Wu; Lunzhu Danzeng; Yang Sun (International Journal of Climatology, 2023)
Hydroclimatic process in Yarlung Zangbo River (YZR) plays a critical role in the water cycle of the whole Tibetan Plateau (TP), but there is a lack of understanding about it due to restrictive conditions. In this study, we further investigate the interannual variation characteristics and possible factors of midsummer (July–August) precipitation in the middle reaches of YZR (MYZR) based on the monthly precipitation data from four stations (Lhasa, Xigaze, Tsedang and Gyangze) in the Inner TP and ERA5 reanalysis dataset for the years 1961–2017. The results suggest that precipitation shows no obvious linear trend during the research period but is dominated by interannual oscillation with evident cycles of 3 years. Meanwhile, the interannual variation of precipitation is related to local changes of water vapour budget. The anomalous anticyclones over the Indian Peninsula‐Southeast Asia continuously transport water vapour from the western Pacific, South China Sea and Bay of Bengal (BOB) to the TP. Simultaneously, both the monsoon low and South Asia high in southern TP provide dynamic conditions for the convergence and uplift of water vapour.

Dark repair of sunlight-inactivated tetracycline-resistant bacteria: Mechanisms and important role of bacteria in viable but non-culturable state - Tingting Zhang; Fangyuan Cheng; Xiaobing Chen; Ya-nan Zhang; Jiao Qu; Jingwen Chen; Willie J.G.M. Peijnenburg (Journal of Hazardous Materials, 2023)

Experimental Study on Motion Characteristics of Cavity Attached to the Tail of Underwater Vehicle - Xiongliang Yao; Zhaoyu Qu; Guihui Ma; Nana Yang; Xiaobo Quan; Shaohua Cheng (Journal of Marine Science and Engineering, 2023)
The formation and development of an attached cavity at the tail of an underwater moving vehicle involves a complex multiphase flow, which determines the load characteristics and motion stability of the vehicle. In this study, an experimental method was used to explore the formation process and motion characteristics of the cavity at the tail of the vehicle, and a pressure sensor installed at the tail of the model was used to establish the relationship between the evolution of the tail attachment cavity and transient pressure. The study found that the process of pulling and breaking the attached cavity was accompanied by the generation of bidirectional jets, and reducing the cavitation number could weaken the occurrence of jet impact. When the ventilation flow reaches the critical value Q¯in = 1.28, the cavity pulsates. In addition, increasing the ventilation flow does not increase the size of the tail cavity, and the length of the cavity at the closure increases with the decrease of the cavitation number.

Calibration and application of high-frequency submersible sub-bottom profiler for deep-sea surficial sediment measurement - Xinghui Cao; Dapeng Zou; Zhiguo Qu; Huancheng Zhen; Hui Cheng; Zhiyi Wei (Marine Georesources & Geotechnology, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Magnetic carbon nanotubes/red phosphorus/graphitic carbon nitride heterojunction for highly efficient visible-light photocatalytic water disinfection - Hao Yang; Dongyang He; Tingting Zhang; Chuanhao Liu; Fangyuan Cheng; Yangjian Zhou; Ya-nan Zhang; Jiao Qu (Chemical Engineering Journal, 2023)

Experimental study on the deterioration characteristics of the remolded loess with Na2SO4 under freezing-thawing cycles - Jian Xu; Zhilang You; Fei Sun; Yanfeng Li; Jianjun Cheng; Lei Qu (Cold Regions Science and Technology, 2023)

ARPC5 is transcriptionally activated by KLF4, and promotes cell migration and invasion in prostate cancer via up-regulating ADAM17 - GenYi Qu; YuLong Zhang; HongTao Duan; Cheng Tang; Guang Yang; Dan Chen; Yong Xu (Apoptosis, 2023)

Decades performance of marine science and education by region and discipline in China - Tianran Hua; Xiao Ruan; Ziyu Qu; Cheng Xue; Shengyun Yang; Yanming Yao; Guanqiong Ye (Frontiers in Marine Science, 2023)
Strengthening scientific research, technological capacity and sustainable use of oceans in developing countries are the goals of the UN’s 2030 Agenda for Sustainable Development. Marine science and education as the key foundation for achieving these goals has been seldom evaluated quantitatively and collectively. This paper adopted the DEA modelling from economics for analyzing the long-term input and output performance of marine science and education at a national scale in China both by region and discipline. It is found that China’s marine science and education level has been improving annually in the last decade. The input/output efficiency of science and education in 11 coastal provinces however has slightly declined except Guangdong. The input/output performance among 14 research disciplines was further evaluated and was found the similar improving trends. The input/output efficiency of 70% research disciplines showed an increasing trend while 30% of which showed a slightly declining trend. The results could provide important references for prioritizing the science and education resources allocation both in different coastal regions and marine research disciplines to save the investment and achieve more progress.

The underlying mechanisms of PM2.5 and O3 synergistic pollution in East China: Photochemical and heterogeneous interactions - Yawei Qu; Tijian Wang; Cheng Yuan; Hao Wu; Libo Gao; Congwu Huang; Yasong Li; Mengmeng Li; Min Xie (Science of The Total Environment, 2023)

Cyclic pentapeptides with anti-inflammatory, cytotoxic or α-glucosidase inhibitory activities from Basidiobolus meristosporus - Cheng Zhao; Jiaojiao Qu; Ruili Lu; Renjie Chen; Quheng Dong; Bo Huang; Guanhu Bao; Fenglin Hu (Phytochemistry, 2023)

LncRNA PVT1 influences breast cancer cells glycolysis through sponging miR-145-5p - Huan Qu; Xingxing Li; Fei Chen; Min Zhang; Xun Lu; Yun Gu; Mingming Lv; Cheng Lu (Genes & Genomics, 2023)
Background Long-non-coding RNA PVT1 (lncRNA PVT1) can be used as an oncogenic regulatory non-coding RNA (ncRNA) for many cancers. However, its function and mechanism in breast cancer (BRCA) are still not clearly elucidated. Objective We attempt to explain the mechanism of PVT1’s role in breast cancer from different perspectives. Methods We analyzed the expression of PVT1 and its correlation with the breast cancer related clinical data in the The Cancer Genome Atlas (TCGA) database. We used PVT1 overexpression and knockdown lentivirus to infect breast cancer MDA-MB-231 cell line for cell function verification, in vitro using CCK-8 to measure proliferation, flow cytometry to measure apoptosis, transwell test to measure invasion and migration ability, detecting cell extracellular acidification rate (ECAR) to assess glycolysis metabolism and explore the biological functions of PVT1 in breast cancer cells. Transcriptome sequencing was used to analyze the changes of related genes in cells after overexpression of PVT1. In vivo we used a xenograft model to study the effect of PVT1 on breast cancer. Results PVT1 was up-regulated in breast cancer tissues and was positively correlated with the clinical stage of breast cancer patients. Overexpression of PVT1 in vitro promoted cell proliferation, migration and invasion, and promoted tumor growth in vivo. Knockdown of PVT1 led to the opposite biological consequence. Further bioinformatics analysis showed that PVT1 changes the glycolysis metabolism of tumors through regulation of glycolysis-related genes. In addition, the expression of miR-145-5p is negatively correlated with PVT1. We consider the possibility of PVT1 promoting cell proliferation and metastasis by regulating the aerobic glucose metabolism in breast cancer cells through sponging the miR-145-5p. Conclusion Our results reveal a potential pathway for competing endogenous RNA to regulate breast cancer glucose metabolism. PVT1 regulates glycolysis related genes expression by competitively binding to endogenous miR-145-5p in breast cancer cells to change the metabolic phenotype. This may Provide new ideas for precise molecular therapy targets for breast cancer.

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Divergent summertime surface O3 pollution formation mechanisms in two typical Chinese cities in the Beijing-Tianjin-Hebei region and Fenwei Plain - Chenlu Li; Feng Li; Qiang Cheng; Yitian Guo; Ziyin Zhang; Xingang Liu; Yu Qu; Junling An; Yafei Liu; Siqing Zhang (Science of The Total Environment, 2023)

Seismic response study of a steel lattice transmission tower considering the hysteresis characteristics of bolt joint slippage - Jia-Xiang Li; Jin-Peng Cheng; Chao Zhang; Chun-Xu Qu; Xiao-Hong Zhang; Wen-Qiang Jiang (Engineering Structures, 2023)

Aggregation-induced color fine-tunable carbon dot phosphorescence covering from green to near-infrared for advanced information encryption - Qijun Li; Dengke Cheng; Hailing Gu; Daiqi Yang; Yuchen Li; Shuai Meng; Yunyang Zhao; Zikang Tang; YiBo Zhang; Jing Tan; Songnan Qu (Chemical Engineering Journal, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Degradation of Bisphonel AF (BPAF) by zero-valent iron activated persulfate: Kinetics, mechanisms, theoretical calculations, and effect of co-existing chloride - Cheng Qin; Yumeng Qi; Xiaolei Teng; Jamaan S. Ajarem; Ahmed A. Allam; Ruijuan Qu (Chemosphere, 2023)

Explicit and size-adaptive PSO-based feature selection for classification - Litao Qu; Weibin He; Jianfei Li; Hua Zhang; Cheng Yang; Bo Xie (Swarm and Evolutionary Computation, 2023)

Mechanisms of synergistic inhibition of NaCl and glycine mixtures on methane hydrate formation: Experimental and molecular dynamic simulation - Jianlong Wang; Jinsheng Sun; Ren Wang; Rongchao Cheng; Bo Liao; Yuanzhi Qu; Qibing Wang; Jintang Wang; Kaihe Lv (Gas Science and Engineering, 2023)

Single-kernel classification of deoxynivalenol and zearalenone contaminated maize based on visible light imaging under ultraviolet light excitation combined with polarized light imaging - Maozhen Qu; Shijie Tian; Hengjie Yu; Da Liu; Chao Zhang; Yingchao He; Fang Cheng (Food Control, 2023)

The impact of heating rate on the decomposition kinetics and product distribution of algal waste pyrolysis with in-situ weight measurement - Muxuan Li; Ye Shui Zhang; Shuo Cheng; Boyu Qu; Aimin Li; Fandongkun Meng; Guozhao Ji (Chemical Engineering Journal, 2023)

Hydrophobic polymer interlayer for highly efficient and stable perovskite solar cells - Qu Yang; Xiu Gong; Xiaosi Qi; Xuncheng Liu; Cheng Liu; Quanfeng Zhou; Qiang Sun; Yan Shen; Mingkui Wang (Chemical Engineering Journal, 2023)

Structure–performance correlation guided cerium-based metal–organic frameworks: Superior adsorbents for fluoride removal in water - Xiaofeng Tang; Wu Xia; Xiaolin Qu; Chaohai Wang; Wenjun Wang; Yuntao Liang; Yuxi Zeng; Weiping Xiong; Min Cheng; Biao Song; Chengyun Zhou; Xiaoying Zhao (Chemosphere, 2023)

Corrigendum to “Grafting with an invasive Xanthium strumarium improves tolerance and phytoremediation of native congener X. sibiricum to cadmium/copper/nickel tailings” [Chemosphere, 308 (2022) 136561] - Chenyang Xue; Lizong Sun; Bo Qu; Yingmei Gao; Zhi Liu; Cheng Guo; Wanbin Liu; Wenyue Chang; Peidong Tai (Chemosphere, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Analytical method for the kinematic response and signal error of a downhole seismometer subjected to P-waves - Changwei Yang; Cheng Yuan; Liming Qu; Xuanming Ding (Soil Dynamics and Earthquake Engineering, 2023)

Promoting the overall energy profit through using the liquid hydrolysate during microwave hydrothermal pretreatment of wheat straw as co-substrate for anaerobic digestion - Zhuangzhuang Zhao; Zhijiang Shao; Qiang Qu; Mengqin Ji; Demin Cheng; Xiaohui Guo (Science of The Total Environment, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Experimental study on ventilated cavity flow at the tail of underwater vehicle under low surface tension - Zhaoyu Qu; Nana Yang; Guihui Ma; Xiongliang Yao; Wangkai Zhang; Hongtu Zhang; Shaohua Cheng; Xiaobo Quan; Yingyu Chen (Ocean Engineering, 2023)

Comprehensive evaluation method of urban air quality statistics based on environmental monitoring data and its application - Linglu Qu; Fahe Chai; Shijie Liu; Jingchun Duan; Fan Meng; Miaomiao Cheng (Journal of Environmental Sciences, 2023)

Improveament of multiple attenuation and optimized impedance gradient for excellent multilayer microwave absorbers derived from two-dimensional metal–organic frameworks - Junjie Pan; Xinji Li; Wei Xia; Hongjiao Qu; Jingjing Li; Cheng Jiang; Tao Wang; Jianping He (Chemical Engineering Journal, 2023)

Oxygen-vacancy-induced charge localization and atomic site activation in ultrathin Bi4O5Br2 nanotubes for boosted CO2 photoreduction - Danjun Mao; Yuan Hu; Shuxue Yang; Jianli Liang; Huan He; Shaogui Yang; Zhaoyi Xu; Cheng Sun; Shourong Zheng; Zhifeng Jiang; Xiaolei Qu; Chun-Sing Lee (Chemical Engineering Journal, 2023)

Microscopic molecular insights into methane hydrate growth on the surfaces of clay minerals: Experiments and molecular dynamics simulations - Ren Wang; Bo Liao; Jintang Wang; Jinsheng Sun; Yudou Wang; Jianlong Wang; Qibing Wang; Yuanzhi Qu; Rongchao Cheng (Chemical Engineering Journal, 2023)

Chitosan enhanced the stability and antibiofilm activity of self-propelled Prussian blue micromotor - Xiaoli Zhang; Qingli Qu; Anquan Yang; Jing Wang; Weixia Cheng; Yankang Deng; Aying Zhou; Tao Lu; Ranhua Xiong; Chaobo Huang (Carbohydrate Polymers, 2023)

Genomic and phenotypic changes associated with alterations of migratory behaviour in a songbird - Dezhi Zhang; Huishang She; Frank E. Rheindt; Lei Wu; Huan Wang; Kai Zhang; Yalin Cheng; Gang Song; Chenxi Jia; Yanhua Qu; Urban Olsson; Per Alström; et al. (Molecular Ecology, 2023)
The seasonal migration of birds is a fascinating natural wonder. Avian migratory behaviour changes are common and are probably a polygenic process as avian migration is governed by multiple correlated components with a variable genetic basis. However, the genetic and phenotypic changes involving migration changes are poorly studied. Using one annotated near‐chromosomal level de novo genome assembly, 50 resequenced genomes, hundreds of morphometric data and species distribution information, we investigated population structure and genomic and phenotypic differences associated with differences in migratory behaviour in a songbird species, Yellow‐throated Bunting Emberiza elegans (Aves: Emberizidae). Population genomic analyses reveal extensive gene flow between the southern resident and the northern migratory populations of this species. The hand‐wing index is significantly lower in the resident populations than in the migratory populations, indicating reduced flight efficiency of the resident populations. Here, we discuss the possibility that nonmigratory populations may have originated from migratory populations though migration loss. We further infer that the alterations of genes related to energy metabolism, nervous system and circadian rhythm may have played major roles in regulating migration change. Our study sheds light on phenotypic and polygenic changes involving migration change.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Spatial-temporal characteristics and driving factors of the chemical fertilizer supply/demand correlation network in China - Hongjiao Qu; Yajing Yin; Wenwen Xing; Weiyin Wang; Cheng Zhou; Junli Li (Environmental Science and Pollution Research, 2022)

Isolation, identification, and quantification of triterpene saponins in the fresh fruits of Panax notoginseng - Zheng-yi Qu; He-cheng Wang; Yin-ping Jin; Ya-li Li; Ying-ping Wang (Natural Product Research, 2022)

Buffer effect of MgO on Na2SO3 to stabilize S(IV) for the enhancement in simultaneous absorption of NOx and SO2 from non-ferrous smelting gas - Wenjun Huang; Sichao Li; Hongbin Wang; Peng Cui; Haomiao Xu; Can Cheng; Zan Qu; Naiqiang Yan (Environmental Science and Pollution Research, 2022)

Control, Treatment and Restoration of Contaminated Soils - Hong-Bo Li; Changsheng Qu; Xinyi Cui; Yang Song; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2022)

Bioaccessibility and Toxicity Assessment of Polycyclic Aromatic Hydrocarbons in Two Contaminated Sites - Huihui Cao; Xiaona Li; Changsheng Qu; Meng Gao; Hu Cheng; Ni Ni; Shi Yao; Yongrong Bian; Chenggang Gu; Xin Jiang; Yang Song (Bulletin of Environmental Contamination and Toxicology, 2022)

Mechanical failure analysis during direct shear of double-joint rock mass - Feng Jiang; Gang Wang; Peng He; Bin Hou; Shu-bo Zhang; Shang-qu Sun; Cheng-cheng Zheng; Yue Wu (Bulletin of Engineering Geology and the Environment, 2022)

Dolominol a and B, two new neolignans from Dolomiaea souliei (Franch.) C.Shih - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Jing-Xin Mao; Guowei Wang; Mingxing Liu; Zhi-Hua Liao; Min Chen (Natural Product Research, 2022)

Comparative Analysis of miRNA Expression Profiles Provides Insight into Regulation of Biosynthesis of Flavonoids and Terpenoids Between Two Varieties of Toona sinensis Sprouts - Hu Zhao; Xiaopu Shi; Cheng Shen; Caifeng Chen; Changqing Qu; Gopal Patel; Wei Zhou; Guoyin Kai (Journal of Plant Biology, 2022)

Spatio-temporal Evolution of the Agricultural Eco-efficiency Network and Its Multidimensional Proximity Analysis in China - Hongjiao Qu; Yajing Yin; Junli Li; Wenwen Xing; Weiyin Wang; Cheng Zhou; Yunhua Hang (Chinese Geographical Science, 2022)

Sevoflurane inhibits the malignant phenotypes of glioma through regulating miR-146b-5p/NFIB axis - Haili Wang; Guofang Cheng; Lili Quan; Haibo Qu; Ailing Yang; Jiangge Ye; Yuanbo Feng; Xiaofang Li; Xiaoli Shi; Hua Pan (Metabolic Brain Disease, 2022)

Targeting iNOS Alleviates Early Brain Injury After Experimental Subarachnoid Hemorrhage via Promoting Ferroptosis of M1 Microglia and Reducing Neuroinflammation - Wenhao Qu; Ying Cheng; Wei Peng; Yan Wu; Tongyu Rui; Chengliang Luo; Jian Zhang (Molecular Neurobiology, 2022)

Comparison of separated and combined photodegradation and biofiltration technology for the treatment of volatile organic compounds: A critical review - Meng-Fei Han; Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Zhuo-Wei Cheng; Ke Feng; Miao-Miao Qu; Jian-Meng Chen; Ji-Guang Deng; Hsing-Cheng Hsi (Critical Reviews in Environmental Science and Technology, 2022)

Galectin-1 Contributes to Vascular Remodeling and Blood Flow Recovery After Cerebral Ischemia in Mice - Yin-hong Cheng; Yi-fan Jiang; Chuan Qin; Ke Shang; Yuan Yuan; Xian-jie Wei; Zhe Xu; Xiang Luo; Wei Wang; Wen-sheng Qu (Translational Stroke Research, 2022)

The combined toxicity of binary mixtures of antibiotics against the cyanobacterium Microcystis is dose-dependent: insight from a theoretical nonlinear combined toxicity assessment method - Yeyong Wang; Cheng Gao; Zhi Qu; Ming Li (Environmental Science and Pollution Research, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Transformation of bisphenol AF by chlorination: kinetic study and product identification - Jingyi Chang; Wenrui Xiang; Ruijuan Qu; Cheng Sun; Zunyao Wang; Feng Zhu; Zongli Huo (Environmental Science and Pollution Research, 2021)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

Dynamic mechanical behavior and damage constitutive model of shales with different bedding under compressive impact loading - Xueru Fan; Ning Luo; Yishuo Yuan; Hanliang Liang; Cheng Zhai; Zhe Qu; Ming Li (Arabian Journal of Geosciences, 2021)

Temperature-induced changes in the proteome of Pseudomonas aeruginosa during petroleum hydrocarbon degradation - Jun-Di Wang; Cheng-Tun Qu; Shao-Fu Song (Archives of Microbiology, 2021)

Oxidation of benzophenone-3 in aqueous solution by potassium permanganate: kinetics, degradation products, reaction pathways, and toxicity assessment - Wanming Cao; Nannan Wu; Ruijuan Qu; Cheng Sun; Zongli Huo; Jamaan S. Ajarem; Ahmed A. Allam; Zunyao Wang; Feng Zhu (Environmental Science and Pollution Research, 2021)

Early Cretaceous continent basalts in the Alxa Block, NW China: geochronology, geochemistry, and tectonic implications - Jie Hui; Hongyi Cheng; Jin Zhang; Kaijun Zhang; Junfeng Qu; Beihang Zhang (International Geology Review, 2021)

Impact factors of the accumulation, migration and spread of antibiotic resistance in the environment - Zibo Lin; Tao Yuan; Lai Zhou; Sen Cheng; Xu Qu; Ping Lu; Qiyan Feng (Environmental Geochemistry and Health, 2021)

Neuronal Protein Farnesylation Regulates Hippocampal Synaptic Plasticity and Cognitive Function - Wenhui Qu; Kiall F. Suazo; Wenfeng Liu; Shaowu Cheng; Angela Jeong; David Hottman; Li-Lian Yuan; Mark D. Distefano; Ling Li (Molecular Neurobiology, 2021)

Morphological and anatomical characteristics of exserted stigma sterility and the location and function of SlLst (Solanum lycopersicum Long styles) gene in tomato - Mo-zhen Cheng; Chao Gong; Bo Zhang; Wei Qu; Hao-nan Qi; Xiu-ling Chen; Xing-yuan Wang; Yao Zhang; Jia-yin Liu; Xiao-dong Ding; You-wen Qiu; Ao-xue Wang (Theoretical and Applied Genetics, 2021)

miR-9-5p facilitates hepatocellular carcinoma cell proliferation, migration and invasion by targeting ESR1 - Libing Wang; Mingxin Cui; Daming Cheng; Fengzhi Qu; Jingkun Yu; Yanbin Wei; Ling Cheng; Xiaotang Wu; Xiaogang Liu (Molecular and Cellular Biochemistry, 2021)

Dual Mechanism of a New SMN1 Variant (c.835G>C, p.Gly279Arg) by Interrupting Exon 7 Skipping and YG Oligomerization in Causation of Spinal Muscular Atrophy - JinLi Bai; YuJin Qu; Fang Song; YanYan Cao; Miaomiao Cheng; Jia Wang; YuWei Jin; Hong Wang (Journal of Molecular Neuroscience, 2021)

Great journey of Great Tits (Parus major group): Origin, diversification and historical demographics of a broadly distributed bird lineage - Gang Song; Ruiying Zhang; Fernando Machado‐Stredel; Per Alström; Ulf S. Johansson; Martin Irestedt; Herman L. Mays; Bailey D. McKay; Isao Nishiumi; Yalin Cheng; Yanhua Qu; Per G. P. Ericson; et al. (Journal of Biogeography, 2020)
Aim The Pleistocene glacial cycles play a prominent role in shaping phylogeographical patterns of organisms, while few studies have focused on the regional difference of glacial effects. By acquiring comprehensive knowledge of the origin, diversification and historical demography of an intensively studied passerine species complex, Great Tit, we aim to test the regional variation of the Late Pleistocene glaciation impacts on this widely distributed bird lineage. Location Eurasia and associated peninsulas and archipelagos. Taxa Parus major species complex. Methods Phylogeny, divergence times and demographic dynamics were estimated with Bayesian methods. Population structure, genetic diversity and correlation between genetic and physical distances were estimated based on mtDNA variation. Glacial‐to‐present distributional changes were assessed via ecological niche modelling (ENM). Results Five major clades (Central Asia, Eastern Asia, Eastern Himalaya, Northern and Western Eurasia and Southern Asia) were detected, with divergence times ranging 1.57–0.50 million years ago. Genetic diversity values and Bayesian skyline plots suggest that the three eastern clades had a deeper population history. A more complex geographic structure was observed in East Asia. Demographic expansion during the last glacial cycle was indicated for all five clades. ENM results showed broad conservatism of traits related to climate tolerances, and generally broader and more continuous distributional patterns under glacial conditions. Main Conclusions The Great Tit complex probably originated in Southeast Asia. Geographic barriers, such as the deserts of Central Asia and the Qinghai–Tibet Plateau appear to be related to the lineage divergence. Late Pleistocene climate cycles influenced both demographic dynamics and divergence, especially in terms of east–west differences in relation to geographic complexity.

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

A new neolignan glycoside from Dolomiaea souliei - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Yun-Yi Tao; Zhi-Hua- Liao; Min Chen (Natural Product Research, 2020)

The roles of moisture transports in intraseasonal precipitation during the preflood season over South China - Qu‐cheng Chu; Qi‐guang Wang; Guo‐lin Feng (International Journal of Climatology, 2020)
The roles of moisture sources and transport in intraseasonal precipitation variabilities during the preflood season over South China are complex and different. In this paper, ERA‐Interim reanalysis data that were collected four times daily from 1979 to 2017 are used to analyse the variation and influence of moisture transport in intraseasonal precipitation during the preflood season over South China. Using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model, fixed atmospheric moisture sources are defined: land area source (LD source), Indian Ocean source (IO source), Pacific Ocean source (PO source), South China Sea source (SCS source), and South China source (SC source). Sea source moisture transport accounts for more than 75% of the total precipitation during the preflood season, which is the most important moisture source in South China. For April, southeasterly moisture transport, which includes PO source and SCS source moisture transports, is the major moisture transport over South China. Then, the IO source and SCS source precipitation increased significantly during May. During June, the IO source precipitation accounted for 43.75% of the total precipitation, thus dominating precipitation over South China. In addition, there is a significant difference in the interdecadal variation in the preflood season precipitation before and after the Indian summer monsoon onset. Before the Indian summer monsoon onset, the land‐sea thermal contrast decreased, which led to a significant interdecadal reduction in the IO source, PO source, and SCS source moisture transports. After the Indian summer monsoon onset, the increase in IO source moisture transport is the primary cause of the interdecadal increase in precipitation over South China.

Complete Genome Sequence of Strain YCSC6, a Marine Bacterium Isolated from Saturated Saltpan with Activity Against Uronema marinum - Guang Xun Du; Ling Yun Qu; Kun Shang; Ping Gao; De Wen Ding; Cheng Jun Sun (Current Microbiology, 2020)

A Global Proteomic Change in Petroleum Hydrocarbon-Degrading Pseudomonas aeruginosa in Response to High and Low Concentrations of Petroleum Hydrocarbons - Jun-Di Wang; Xu-Xiang Li; Cheng-Tun Qu (Current Microbiology, 2019)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

From Analysis of Ischemic Mouse Brain Proteome to Identification of Human Serum Clusterin as a Potential Biomarker for Severity of Acute Ischemic Stroke - Hailong Song; Hui Zhou; Zhe Qu; Jie Hou; Weilong Chen; Weiwu Cai; Qiong Cheng; Dennis Y. Chuang; Shanyan Chen; Shuwei Li; Jilong Li; Jianlin Cheng; et al. (Translational Stroke Research, 2019)

The mechanism of damage in the midgut of Bombyx mori after chlorantraniliprole exposure - Jiahuan Hu; Mengxue Li; Zhengting Lu; Tingting Mao; Jian Chen; Hui Wang; Jianwei Qu; Yilong Fang; Xiaoyu Cheng; Jinxin Li; Fanchi Li; Bing Li (Ecotoxicology, 2019)

Branched-chain amino acids regulate plant growth by affecting the homeostasis of mineral elements in rice - Cheng Jin; Yangyang Sun; Yuheng Shi; Yuanyuan Zhang; Kai Chen; Yuan Li; Guige Liu; Fang Yao; Deng Cheng; Jie Li; Junjie Zhou; Lianghuan Qu; et al. (Science China Life Sciences, 2019)

Digitizing and modeling of structural planes in fractured rock mass tunnel based on SfM - Shang-qu Sun; Li-ping Li; Cheng-shuai Qin; Hong-liang Liu; Yan-huan Zhang; Xing-zhi Ba (Arabian Journal of Geosciences, 2019)

Seasonal behavior of water-soluble organic nitrogen in fine particulate matter (PM2.5) at urban coastal environments in Hong Kong - Steven Sai Hang Ho; Lijuan Li; Linli Qu; Junji Cao; Ka Hei Lui; Xinyi Niu; Shun-Cheng Lee; Kin Fai Ho (Air Quality, Atmosphere & Health, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

Optimization of Hydrolysis Conditions for the Isolation of Angiotensin-I Converting Enzyme (ACE) Inhibitory Peptides from Rhopilema hispidum - Zhenliang Sun; Huanlong Qin; Duo Cao; Xuebing Yan; Hao Li; Linsheng Huang; Xiao Qu; Cheng Kong; Man Wang (Journal of Ocean University of China, 2018)

Influence of Atmospheric Particulate Matter on Ozone in Nanjing, China: Observational Study and Mechanistic Analysis - Yawei Qu; Tijian Wang; Yanfeng Cai; Shekou Wang; Pulong Chen; Shu Li; Mengmeng Li; Cheng Yuan; Jing Wang; Shaocai Xu (Advances in Atmospheric Sciences, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Iodine-Rich Herbs and Potassium Iodate Have Different Effects on the Oxidative Stress and Differentiation of TH17 Cells in Iodine-Deficient NOD.H-2h4 Mice - Cheng-han Gao; Jin-qiao Qu; Xi-yu Zhou; Tian-shu Gao (Biological Trace Element Research, 2018)

Early middle Holocene climate oscillations recorded in the Beihuqiao Core, Yuhang, Zhejiang Province, China - Wei Ye; Qu Chen; Lidong Zhu; Fengquan Li; Tianyang Wang; Longjuan Cheng; Yunxia Zhang (Journal of Paleolimnology, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Genomic differentiation and patterns of gene flow between two long‐tailed tit species ( Aegithalos ) - Dezhi Zhang; Gang Song; Bin Gao; Yalin Cheng; Yanhua Qu; Shaoyuan Wu; Shimiao Shao; Yongjie Wu; Per Alström; Fumin Lei (Molecular Ecology, 2017)
Patterns of heterogeneous genomic differentiation have been well documented between closely related species, with some highly differentiated genomic regions (“genomic differentiation islands”) spread throughout the genome. Differential levels of gene flow are proposed to account for this pattern, as genomic differentiation islands are suggested to be resistant to gene flow. Recent studies have also suggested that genomic differentiation islands could be explained by linked selection acting on genomic regions with low recombination rates. Here, we investigate genomic differentiation and gene‐flow patterns for autosomes using RAD ‐seq data between two closely related species of long‐tailed tits ( Aegithalos bonvaloti and A. fuliginosus ) in both allopatric and contact zone populations. The results confirm recent or ongoing gene flow between these two species. However, there is little evidence that the genomic regions that were found to be highly differentiated between the contact zone populations are resistant to gene flow, suggesting that differential levels of gene flow is not the cause of the heterogeneous genomic differentiation. Linked selection may be the cause of genomic differentiation islands between the allopatric populations with no or very limited gene flow, but this could not account for the heterogeneous genomic differentiation between the contact zone populations, which show evidence of recent or ongoing gene flow.

The in vitro photodynamic activity, photophysical and photochemical research of a novel chlorophyll-derived photosensitizer - Guanghui Tan; Qi Wang; Hongyue Zhang; Jianjun Cheng; Zhiqiang Wang; Fengyu Qu; Changhong Guo; Yingxue Jin (Medicinal Chemistry Research, 2017)

Exploration of Up-regulated Key Proteins in Pseudomonas Aeruginosa for High-efficiency Petroleum Degradation by Proteomic Analysis - Jun-Di Wang; Xu-Xiang Li; Cheng-Tun Qu (Current Microbiology, 2017)

Development of Fluorescence-Linked Immunosorbent Assay for Icariin - Jinjun Cheng; Yan Zhao; Meiling Zhang; Yue Zhang; Xiaoman Liu; Xin Yan; Yongzhi Wang; Ziwei Sun; Qingguo Wang; Huihua Qu (Journal of Fluorescence, 2017)

Coumarin-Based Fluorescent Probe for Hypochlorites and Real Application in Tap Water - Xiaohong Cheng; Shaohua Qu; Zhicheng Zhong; Wangnan Li (Journal of Fluorescence, 2017)

Characterization and complete genome sequence analysis of a novel virulent Siphoviridae phage against Staphylococcus aureus isolated from bovine mastitis in Xinjiang, China - Qian Zhang; Shaozhen Xing; Qiang Sun; Guangqian Pei; Shi Cheng; Yannan Liu; Xiaoping An; Xianglilan Zhang; Yonggang Qu; Yigang Tong (Virus Genes, 2017)

Isolation and characterization of twenty-nine novel EST-SSR markers in Siniperca undulata - CHUN-MEI QU; XU-FANG LIANG; WEI HUANG; CHENG ZHAO; LIANG CAO (Journal of Genetics, 2016)

Development and characterization of twenty-nine novel polymorphic microsatellite loci in the mandarin fish Siniperca chuatsi - CHUN-MEI QU; XU-FANG LIANG; WEI HUANG; CHENG ZHAO; LIANG CAO; MIN YANG; CHANG-XU TIAN (Journal of Genetics, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Influence of ginseng cultivation under larch plantations on plant diversity and soil properties in Liaoning Province, Northeast China - Wei-wei Liu; Mou-cheng Liu; Wen-hua Li; Fan-shun Zeng; Yi Qu (Journal of Mountain Science, 2016)

Effect of operation parameters on the flux stabilization of gravity-driven membrane (GDM) filtration system for decentralized water supply - Xiaobin Tang; An Ding; Fangshu Qu; Ruibao Jia; Haiqing Chang; Xiaoxiang Cheng; Bin Liu; Guibai Li; Heng Liang (Environmental Science and Pollution Research, 2016)

A green vendor-managed inventory analysis in supply chains under carbon emissions trading mechanism - Yushan Jiang; Bo Li; Xiaolong Qu; Yuepeng Cheng (Clean Technologies and Environmental Policy, 2016)

Distribution Characteristics, Concentrations, and Sources of Cd and Pb in Laoxiawan Channel Sediments from Zhuzhou, China - Wen-wen Chen; Jian-xin Zhang; Olusegun-kazeem Abass; Xin-yu Wen; Huan-fang Huang; Cheng-kai Qu; Shi-hua Qi (Bulletin of Environmental Contamination and Toxicology, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Levels and distribution of organochlorine pesticides and hexachlorobutadiene in soils and terrestrial organisms from a former pesticide-producing area in Southwest China - Zhenwu Tang; Qifei Huang; Zhiqiang Nie; Yufei Yang; Jun Yang; Dan Qu; Jiali Cheng (Stochastic Environmental Research and Risk Assessment, 2016)

PRL-3 promotes gastric cancer migration and invasion through a NF-κB-HIF-1α-miR-210 axis - Cheng Zhang; Wei Tian; Lin Meng; Like Qu; Chengchao Shou (Journal of Molecular Medicine, 2016)

Reactive oxygen species regulate programmed cell death progress of endosperm in winter wheat (Triticum aestivum L.) under waterlogging - Xiang-Xu Cheng; Min Yu; Nan Zhang; Zhu-Qing Zhou; Qiu-Tao Xu; Fang-Zhu Mei; Liang-Huan Qu (Protoplasma, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.

CarHSFB2, a Class B Heat Shock Transcription Factor, Is Involved in Different Developmental Processes and Various Stress Responses in Chickpea (Cicer Arietinum L.) - Hao Ma; Chuntao Wang; Bin Yang; Huiying Cheng; Ze Wang; Abudoukeyumu Mijiti; Cai Ren; Guanghang Qu; Hua Zhang; Lin Ma (Plant Molecular Biology Reporter, 2016)

Paeoniflorin exerts analgesic and hypnotic effects via adenosine A1 receptors in a mouse neuropathic pain model - Dou Yin; Yuan-Yuan Liu; Tian-Xiao Wang; Zhen-Zhen Hu; Wei-Min Qu; Jiang-Fan Chen; Neng-Neng Cheng; Zhi-Li Huang (Psychopharmacology, 2016)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Applications of Near-infrared Spectroscopy in Food Safety Evaluation and Control: A Review of Recent Research Advances - Jia-Huan Qu; Dan Liu; Jun-Hu Cheng; Da-Wen Sun; Ji Ma; Hongbin Pu; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Development of a Fluorescence-Linked Immunosorbent Assay for Baicalin - Wenchao Shan; Jinjun Cheng; Baoping Qu; Jiayang Sai; Hui Kong; Huihua Qu; Yan Zhao; Qingguo Wang (Journal of Fluorescence, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Development of Fluorescence-Linked Immunosorbent Assay for Paeoniflorin - Yan Zhao; Huihua Qu; Xueqian Wang; Yue Zhang; Jinjun Cheng; Yan Zhao; Qingguo Wang (Journal of Fluorescence, 2015)

Mesenchymal stem cells inhibit Th17 cells differentiation via IFN-γ-mediated SOCS3 activation - Xingxia Liu; Shaoda Ren; Xuebin Qu; Chaozhuo Ge; Kai Cheng; Robert Chun Hua Zhao (Immunologic Research, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

A SNP in OsMCA1 responding for a plant architecture defect by deactivation of bioactive GA in rice - Zhenwei Liu; Qin Cheng; Yunfang Sun; Huixia Dai; Gaoyuan Song; Zhibin Guo; Xuefeng Qu; Daiming Jiang; Chuan Liu; Wei Wang; Daichang Yang (Plant Molecular Biology, 2015)

Genetic association study between INSULIN pathway related genes and high myopia in a Han Chinese population - Xiaoqi Liu; Pu Wang; Chao Qu; Hong Zheng; Bo Gong; Shi Ma; He Lin; Jing Cheng; Zhenglin Yang; Fang Lu; Yi Shi (Molecular Biology Reports, 2015)

Piromelatine exerts antinociceptive effect via melatonin, opioid, and 5HT1A receptors and hypnotic effect via melatonin receptors in a mouse model of neuropathic pain - Yuan-Yuan Liu; Dou Yin; Li Chen; Wei-Min Qu; Chang-Rui Chen; Moshe Laudon; Neng-Neng Cheng; Yoshihiro Urade; Zhi-Li Huang (Psychopharmacology, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Towards a common validation sample set for global land-cover mapping - Yuanyuan Zhao; Peng Gong; Le Yu; Luanyun Hu; Xueyan Li; Congcong Li; Haiying Zhang; Yaomin Zheng; Jie Wang; Yongchao Zhao; Qu Cheng; Caixia Liu; et al. (International Journal of Remote Sensing, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Deficiency of MTMR14 promotes autophagy and proliferation of mouse embryonic fibroblasts - Jing Liu; Yin Lv; Qing-hua Liu; Cheng-Kui Qu; Jinhua Shen (Molecular and Cellular Biochemistry, 2014)

Sirt1 Promotes Axonogenesis by Deacetylation of Akt and Inactivation of GSK3 - Xiao-hong Li; Chong Chen; Yue Tu; Hong-tao Sun; Ming-liang Zhao; Shi-xiang Cheng; Yang Qu; Sai Zhang (Molecular Neurobiology, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Isolation and characterization of 31 polymorphic microsatellite markers in Siniperca obscura Nichols - Wei Huang; Xu-Fang Liang; Chun-Mei Qu; Cheng Zhao; Liang Cao (Conservation Genetics Resources, 2013)

Development and characterization of novel polymorphic microsatellite loci in Siniperca scherzeri Steindachner and Siniperca chuatsi (Basilewsky) - Wei Huang; Xufang Liang; Chunmei Qu; Jingjing Cao; Cheng Zhao; Liang Cao (Molecular Biology Reports, 2013)

Two phthalide dimers from the radix of Angelica sinensis - Xing-Nuo Li; Yuan-Yi Chen; Dong-Ping Cheng; Sheng-Qiang Tong; Hai-Bin Qu; Ji-Zhong Yan (Natural Product Research, 2012)

Analysis of expressed sequence tags from grapevine flower and fruit and development of simple sequence repeat markers - Xi-Cheng Wang; Lei Guo; Ling-Fei Shangguan; Chen Wang; Guang Yang; Shen-Chun Qu; Jing-Gui Fang (Molecular Biology Reports, 2012)

Up-regulation of growth factor independence 1 in endotoxin tolerant macrophages with low secretion of TNF-α and IL-6 - Min-Fang Zhu; Jing Zhang; Jie-Ming Qu; Hui-Jun Zhang; Shuang-Cheng Zhou; Sheng-Fu Dong; Hong-Ni Jiang; Hanssa Summah (Inflammation Research, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii - Yu Cheng Wang; Guan Zheng Qu; Hong Yan Li; Ying Jie Wu; Chao Wang; Gui Feng Liu; Chuan Ping Yang (Molecular Biology Reports, 2010)

Recruitment of AtWHY1 and AtWHY3 by a distal element upstream of the kinesin gene AtKP1 to mediate transcriptional repression - Ji-Yuan Xiong; Cheng-Xia Lai; Zhe Qu; Xue-Yong Yang; Xing-Hua Qin; Guo-Qin Liu (Plant Molecular Biology, 2009)

Numerical simulation of impact on pneumatic DTH hammer percussive drilling - Changgen Bu; Yegao Qu; Zhiqiang Cheng; Baolin Liu (Journal of Earth Science, 2009)

Glucosamine sulphate does not increase extracellular matrix production at low oxygen tension - Cheng-Juan Qu; Teemu Pöytäkangas; Marjo Jauhiainen; Seppo Auriola; Mikko J. Lammi (Cell and Tissue Research, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Identification and Experimental Verification of Protective Antigens Against Streptococcus suis Serotype 2 Based on Genome Sequence Analysis - Lina Liu; Gong Cheng; Changjun Wang; Xiuzhen Pan; Yanguang Cong; Qu Pan; Jing Wang; Feng Zheng; Fuquan Hu; Jiaqi Tang (Current Microbiology, 2009)

Simultaneous detection of seven phenolic acids in Danshen injection using HPLC with ultraviolet detector - Jin-zhong Xu; Jie Shen; Yi-yu Cheng; Hai-bin Qu (Journal of Zhejiang University-SCIENCE B, 2008)

Expression and colocalization of NADPH-diaphorase and heme oxygenase-2 in trigeminal ganglion and mesencephalic trigeminal nucleus of the rat - Wenguo Fan; Weiguo Dong; Shuilong Leng; Dongpei Li; Shaowu Cheng; Cuixia Li; Huaigang Qu; Hongwen He (Journal of Molecular Histology, 2008)

Discovering active compounds from mixture of natural products by data mining approach - Yi Wang; Yecheng Jin; Chenguang Zhou; Haibin Qu; Yiyu Cheng (Medical & Biological Engineering & Computing, 2008)

Metabonomic analysis of hepatitis B virus-induced liver failure: identification of potential diagnostic biomarkers by fuzzy support vector machine - Yong Mao; Xin Huang; Ke Yu; Hai-bin Qu; Chang-xiao Liu; Yi-yu Cheng (Journal of Zhejiang University-SCIENCE B, 2008)

Influence of vertical eddy diffusivity parameterization on daily and monthly mean concentrations of O3 and NOy - Junling An; Xinjin Cheng; Yu Qu; Yong Chen (Advances in Atmospheric Sciences, 2007)

An experimental study of the mechanisms of freeze/thaw and wind erosion of ancient adobe buildings in northwest China - Jian-Jun Qu; Guo-Dong Cheng; Ke-Cun Zhang; Jia-Cheng Wang; Rui-Ping Zu; Hai-Yan Fang (Bulletin of Engineering Geology and the Environment, 2007)

Mercury pollution in two typical areas in Guizhou province, China and its neurotoxic effects in the brains of rats fed with local polluted rice - Jinping Cheng; Tao Yuan; Wenhua Wang; Jinping Jia; Xueyu Lin; Liya Qu; Zhenhua Ding (Environmental Geochemistry and Health, 2006)

Development of intermediate foodstuff derived from freshwater fish in China - Xichang Wang; Yutaka Fukuda; Shunsheng Chen; Masahito Yokoyama; Yudong Cheng; Chunhong Yuan; Yinghong Qu; Morihiko Sakaguchi (Journal of Ocean University of China, 2005)

Priorities for the conservation of avian biodiversity in China based on the distribution patterns of endemic bird genera - Fu-Min Lei; Yan-Hua Qu; Qian-Qian Tang; Shu-Cheng An (Biodiversity and Conservation, 2003)

In vitro and in vivo transfection and expression of plasmid-based non-viral vector for erythropoietin gene therapy - Xianmin Zhu; Zhongmei Chu; Yunlong Hu; Jianfeng Lu; Cheng Liu; Xianming Qu; Yi Zhang (Biotechnology Letters, 2002)

A system dynamics approach for sustainable development in the Miyun Reservoir Area, China - Yan-feng Sun; Huai-cheng Guo; Guang-yi Qu (Chinese Geographical Science, 2002)

Raised concentration of serum bile acids following occupational exposure to halogenated solvents, 1,1,2-trichloro-1,2,2-trifluoroethane and trichloroethylene - Masoud Neghab; Shuxin Qu; Cheng Long Bai; Julian Caples; Neill H. Stacey (International Archives of Occupational and Environmental Health, 1997)